From fragments to full pictures: how long-read sequencing platforms are revolutionizing oncology research - Ruby Dhar; Abhibroto Karmakar; Abhishesh Kumar Badal; Om Saswat Sahoo; Prasmita Paul; Isha Goel; Arnab Nayek; Karthikeyan Pethusamy; Ashikh Seethy; Subhradip Karmakar (Molecular Biology Reports, 2026)

Disparities in Gallbladder Cancer: Epidemiology, Molecular Mechanisms, and Clinical Implications - Om Saswat Sahoo; Gurpeet Singh Gill; Arnab Nayek; Nidhi Bhardwaj; Kailash Chand Kurdia; Saurabh Galodha; R Chetan; Ruby Dhar; Subhradip Karmakar (Molecular Biology Reports, 2026)

Comprehensive transcriptomic analysis highlights immune and cell-cycle dysregulation in Diamond-Blackfan Anaemia - Isha Goel; Ashikh Seethy; Karthikeyan Pethusamy; Deepak Kumar; Ruby Dhar; Tulika Seth; Subhradip Karmakar (Molecular Genetics and Genomics, 2026)

Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

Evolutionary co-option of endogenous retroviruses: syncytins as regulators of placental development and disease - Anamta Gul; Om Saswat Sahoo; Neha Kashyap; Sunil Singh; Anubhuti Rana; Lavanya Gupta; Swati Ajmeriya; Indrani Mukherjee; Ruby Dhar; Nihar R. Nayak; Subhradip Karmakar (Molecular Biology Reports, 2026)

Dependence of subseasonal to seasonal precipitation prediction on atmospheric and land initial conditions in the Energy Exascale Earth System Model - Dongze Xu; Zhaoxia Pu; Shixuan Zhang; Jeffrey Anderson; L. Ruby Leung (Climate Dynamics, 2026)

Mitogenomic Architecture and Phylogenetic Insights Shed Light on the Matrilineal Evolution of the Mahseer Fish Neolissochilus sumatranus (Cyprinidae: Torinae) in Southeast Asia - Sekar Larashati; Angkasa Putra; Sarifah Aini; Gema Wahyudewantoro; Mey Ristanti Widoretno; Dwi Febrianti; Huria Marnis; Imam Civi Cartealy; Tri Widiyanto; Ruby Vidia Kusumah; Anik Budhi Dharmayanthi; Muhammad Hilman Fu’adil Amin; et al. (Biochemical Genetics, 2026)

Mutagenic and carcinogenic potency determinations for NDMA support the cumulative dose assumption underpinning the less-than-lifetime Threshold of Toxicological Concern - John W. Wills; Angela White; Danielle S. G. Harte; Ruby Buckley; James S. Harvey; Anthony M. Lynch (Archives of Toxicology, 2026)

Correction: Establishment of a Cre-rat resource for creating conditional and physiological relevant models of human diseases - Huimin Zhang; Qi Zheng; Ruby Yanru Chen-Tsai (Transgenic Research, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Tourists’ Circular Behavior and Its Determinants: Pathways Toward Sustainable Destinations - Swati Naik; Ruby S. Chanda (Circular Economy and Sustainability, 2026)

Postharvest γ-Aminobutyric Acid Treatment Modulates Antioxidant Metabolism and Delays Quality Deterioration of Litchi Fruit - Nilanksha; Preeti Singh; Hidayatullah Mir; Ruby Rani; Mohammed Wasim Siddiqui; Fozia Homa; Shashi Prakash (Applied Fruit Science, 2026)

miRNA–mRNA network analysis reveals novel post-transcriptional regulators and therapeutic targets in coronary artery disease - Prasmita Paul; Om Saswat Sahoo; Rajiv Narang; Abhishesh Kumar Badal; Arnab Nayek; Ruby Dhar; Oindrilla Mukherjee; Satyavir Yadav; Subhradip Karmakar (Journal of Applied Genetics, 2026)

Abiotic factors influencing the health of mature Araucaria heterophylla (Norfolk Island Pine trees) in urban coastal parks - Anna Petrova; Chris Pratt; Ruby Naomi Michael (Environmental Management, 2026)
Tree decline can significantly impact both the aesthetic value and ecological function of urban forests. Understanding the abiotic factors influencing tree health is essential for developing effective management strategies. This study investigated the decline of heritage Araucaria heterophylla (Norfolk Island Pine) in urban areas of the Gold Coast, Queensland, Australia, with a focus on identifying underlying abiotic causes. General assessment was conducted along a 5-km coastal strip (including 946 trees); climate conditions on the Gold Coast and Norfolk Island were compared; and 38 selected trees of varying health status were examined in detail. This included soil physicochemical and nutrient analysis, as well as foliar nutrient profiling. Results showed that 15.8% of the 946 initially assessed trees exhibited symptoms of decline, such as dieback, browning of foliage tips, extensive defoliation and shortened foliage length. Mean temperatures on the Gold Coast were consistently higher than those in the species’ native range and the current decline followed a period of elevated temperatures and reduced rainfall. Declining trees ( n = 32) from the subset population were found to be growing in compacted soils, with significantly elevated foliar sodium and lower foliar carbon levels compared to healthy trees ( n = 6), indicating possible disruption of nutrient regulation. Half of the trees in the advanced stage of decline were located less than 5 m away from carparks (50%), which was higher when compared with Moderate Decline (18.7%) and very healthy Benchmarking trees (0%). Most trees in the advanced decline category were not mulched and had turfgrass as the primary groundcover (62.5%), whereas trees in moderate decline were more commonly associated with turfgrass combined with fallen branchlets (43.75%). In addition, all Benchmarking trees were located in sandy soils, whereas declining trees were more commonly associated with loam soils, which are more susceptible to compaction. Key abiotic stressors identified were extreme weather and proximity to urban infrastructure. Management recommendations include improving root zone conditions by providing irrigation during dry periods, mulching, implementing routine health monitoring to support early intervention and, for new planting, increasing distances from hard infrastructure.

Correction: Neratinib-loaded solid lipid nanoparticles in dissolvable microneedles for enhanced transdermal breast cancer therapy - Saraisam Kishor Kumar Singha; Venkatesh Dinnekere Puttegowda; Yousef Al-ebini; Mohamed Rahamathulla; Joysa Ruby Joseph; Ajay Pankajbhai Lunagariya; Mohammed Jafar; Syeda Ayesha Farhana; Manjunatha Panduranga Mudughal; Gowdru Vishwanath Nahusha; Mohammed Muqtader Ahmed (Drug Delivery and Translational Research, 2026)

Neratinib-loaded solid lipid nanoparticles in dissolvable microneedles for enhanced transdermal breast cancer therapy - Saraisam Kishor Kumar Singha; Venkatesh Dinnekere Puttegowda; Yousef Al-ebini; Mohamed Rahamathulla; Joysa Ruby Joseph; Ajay Pankajbhai Lunagariya; Mohammed Jafar; Syeda Ayesha Farhana; Manjunatha Panduranga Mudughal; Gowdru Vishwanath Nahusha; Mohammed Muqtader Ahmed (Drug Delivery and Translational Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Strategies to reduce cholesterol content in poultry eggs: an overview - Namrata Balhara; Dimple Dimple; Ruby Ruby; Andrew Magnuson; Arup Giri; Manishi Mukesh (Tropical Animal Health and Production, 2026)

Soil Application of Zinc for Potato Biofortification in the Central Andes of Peru - Fernando Chung-Montoya; Victorio Melendres-Herrera; Vanessa Pilatarzi-Vilchez; Angely Sinche-Ambrosio; Jesús Vera-Vilchez; Ruby Vega-Ravello; Sady García-Bendezú (Journal of Soil Science and Plant Nutrition, 2026)
Zinc is essential for human health, yet dietary deficiencies persist in many regions. This study evaluated the effectiveness of soil-applied zinc to enhance zinc content in potato tubers grown in Peru’s central Andes, as an agronomic biofortification strategy. Field trials were conducted over two seasons in four Andean sites using five Zn rates (0–32 kg ha⁻¹). One variety was tested in 2016–2017, and four in 2017–2018. Yield, Zn content, accumulation, partial balance, and dietary contribution were assessed. In both seasons, Zn fertilization did not significantly affect tuber yield. In 2016–2017, Zn content in tubers increased by up to 86% and accumulation by 74% at 16 kg Zn ha⁻¹. The estimated dietary contribution rose by 79%, with Achoscuyo showing the highest response and Lucma the lowest. Site differences were more evident at intermediate and high doses. In 2017–2018, Zn accumulation in shoots exceeded that in tubers by up to 2.8-fold, and Zn content in the peel was twice that of the flesh. Maximum Zn content and accumulation varied among varieties and doses. Canchán and Perricholi showed high Zn content and accumulation at 16 kg Zn ha⁻¹. Principal component analysis revealed that Zn dose was positively associated with Zn content and negatively with tuber yield. The response to Zn fertilization depended on site, dose, and genotype. Soil-applied Zn increased Zn content in potatoes without compromising yield. Selecting varieties with high tuber Zn accumulation improved nutritional outcomes and fertilizer use efficiency.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Pharmacokinetics and bioavailability of cefuroxime in Nile tilapia (Oreochromis niloticus) - Orhan Corum; Duygu Durna Corum; Pedro Marin; Onder Yildirim; Ertugrul Terzi; Ruby C. Gonzales; Dan M. Arriesgado; Victor R. Navarro; Soner Bilen; Adem Yavuz Sonmez; Kamil Uney (Veterinary Research Communications, 2026)

A holistic guide to effective prevention and treatment for kidney stones: a systematic review exploring anti-urolithiasis approaches - Anood T. Allam; Ahmed M. El-Dessouki; Riham A. El-Shiekh; Dina Abou-Hussein; Mahmoud Abdelmouti Mahmoud; Wagih H. Marcus; Hassan A. Ruby (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Urolithiasis, a disease of kidney stones, is a prevalent and recurrent condition characterized by the formation of hard mineral deposits in the urinary tract, leading to significant morbidity and a substantial healthcare burden worldwide. With recurrence rates ranging from 30 to 50% and a lifetime prevalence of 9–12% in industrialized populations, effective prevention and management strategies are crucial. Traditional approaches to urolithiasis, including pharmacological agents and surgical interventions, emphasize medical interventions and lifestyle changes; however, the persistent recurrence and impact on quality of life underscore the necessity for more comprehensive solutions. Recent advancements have focused on the potential of nutraceuticals, including herbal extracts, vitamins, and minerals, as adjuncts in the prevention and treatment of kidney stones. These agents may exert beneficial effects by inhibiting stone crystal formation, modulating urinary pH, reducing urinary calcium and oxalate excretion, enhancing diuresis, and supporting overall renal function. Moreover, these plant-based therapies may help alleviate symptoms such as pain and inflammation related to stone episodes. This systematic review synthesizes findings from 14 randomized controlled trials to assess the therapeutic impact and safety profile of various herbal interventions in patients with diagnosed kidney or ureteral stones. Thus, evidence from these recent clinical trials has increasingly supported the efficacy of single-herb and polyherbal formulations, such as Nigella sativa , Alhagi maurorum , Subap Plus, and Palasha Kshara, in modulating urinary risk factors and promoting stone expulsion. For instance, these trials demonstrated promising outcomes for several herbs: Portulaca oleracea significantly increased urinary citrate and reduced calcium, Traditional Persian Medicine-based Mofatet powder markedly reduced stone size and improved urinary parameters, Alhagi maurorum distillates and extracts showed comparable efficacy to hydrochlorothiazide in stone expulsion, and Nigella sativa performed as well as or better than tamsulosin in both pain relief and stone passage. Additional polyherbal remedies, such as Subap Plus, Palasha Kshara, and BNO 1040 extract, also yielded favourable results in improving stone clearance, easing symptoms, and potentially preventing recurrence. Notably, most studies reported good short-term tolerability and minimal adverse effects. Despite these promising findings, limitations in sample size, standardization of formulations, lack of comprehensive adverse events reporting, and need for long-term follow-up highlight the necessity for further rigorous trials.

Differential interspecific responses of symbiotic luminous bacteria Vibrio spp. in a cephalopod host to marine heatwaves - Eve Otjacques; Nicolina G. Ranieri; Tiago Repolho; José C. Xavier; Edward Ruby; Margaret McFall-Ngai; Rui Rosa (Marine Biology, 2026)

Environmental monitoring of carbofuran pesticides in wastewater, soil, and food samples using a Co9S8@N, S-doped carbon nanocomposite-engineered voltammetric sensor - Janagaraj Gandhiraj; Kavitha Balasubramanian; Michael Ruby Raj; Saradh Prasad; Khalid Eidah Alzahrani; Murugan Velmurugan; Chelladurai Karuppiah; Subramanian Chidambaravinayagam; Sayee Kannan Ramaraj (Environmental Geochemistry and Health, 2026)

Beyond understanding the role of far-field climate in the Gulf of Panama coastal dynamics: an analysis of long-term and seasonal variability of wave systems - Ruby Vallarino-Castillo; José A. A. Antolínez; Vicente Negro-Valdecantos; Jesús Portilla-Yandún (Climate Dynamics, 2026)
Understanding wave systems (WS) dynamics in semi-enclosed tropical basins is challenging due to interactions between remote wave generation and regional climate variability. In the Gulf of Panama, prior studies mainly relied on single-site offshore analyses, limiting characterization of wave energy distribution and its atmospheric and oceanic drivers. This gap in knowledge is particularly consequential for coastal hazard assessments and for deciphering ocean–atmosphere interactions in regions influenced by both long-period swells and low-level wind jets. To address this limitation, we present a comprehensive multi-decadal analysis of the seasonal and long-term variability of significant wave height (Hs) and peak wave period (Tp), based on WS identified applying spectral statistical techniques using the GLOSWAC-5 atlas. To understand the variability and the modulating effect of the Gulf of Panama semi-enclosed morphology, three representative sites at its entrance were selected. Monthly patterns were analyzed by classifying wave trains according to relative orientation (i.e., following, crossing, and opposing) to determine the predominant direction and multimodal activity. Long-term trends were assessed over 17 to 18-year intervals (i.e. 1969–1987, 1988–2005, 2006–2023) using exploratory analysis and quantile regression, with results reported separately for the dry season (December–April) and the wet season (May–November). The analysis revealed five dominant WS, each associated with specific generation mechanisms and geographic origins: WS1, associated with Southern Ocean swells; WS5, originating from Northern Hemisphere swells; WS2, driven by southeasterly trade winds from the subtropical Pacific; and two regionally forced systems, WS3 and WS4, generated by the Panama and Chocó Low-Level Jets, respectively. WS1 shows increases in Hs of about 5–10 cm during 1969–1987 and 1988–2005, and up to ~ 15 cm in 2006–2023, with Tp rising by ~ 0.3–0.6 s over the same intervals. WS2 exhibits small variations, with Hs ranging from − 10 to + 17 cm and Tp fluctuations within ± 0.3 s across the three intervals. WS3 displays the strongest changes, with median Hs increases of 10–30 cm in the first two intervals and extreme values reaching 50–60 cm in 1988–2005 and 2006–2023, together with Tp increments of ~ 0.3–0.5 s. WS4 remains comparatively stable in all periods, with Hs variations within ± 10 cm and Tp changes < 0.4 s. WS5 intensifies mainly in 2006–2023, showing Hs increases of 8–15 cm and Tp rises of ~ 0.2–0.4 s. Monthly mean Hs anomalies (> 0.10 m) at the 50th percentile suggest a relationship with El Niño–Southern Oscillation (ENSO), but analyses using the 95th percentile reveal that only WS2, WS3, and WS4 exhibit a stronger association with ENSO phases.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Robbers vs. invaders: The effects of alien tree invasions on nectar robbing in bird-pollinated Erica species - Ruby May Davies; Anina Coetzee; Colleen L. Seymour (Journal of Plant Research, 2026)

Integrated Body and Otolith Morphometrics Indicate a Single Stock of Bigeye Scad (Selar crumenophthalmus) in Northern Mindanao, Philippines - Renie M. Magallanes; Lhendy P. De Leon; Rosa Ruby P. Cabiguin; Emmanuel S. Delloro; Adzel Adrian G. Baldevieso; Kaent Immanuel N. Uba (Thalassas: An International Journal of Marine Sciences, 2025)

Condition Does Not Alter Responsiveness to Mating Signals in Female Pacific Field Crickets - Jon Richardson; Ruby Ales; Marlene Zuk (Journal of Insect Behavior, 2025)
Animals often vary in their condition (i.e. the amount of resources allocatable to fitness-related functions) and such variation can influence the expression of important mating behaviors like how quickly individuals respond to mating signals. If individuals in poor condition invest less in finding mates, perhaps because they can’t afford the energetic costs, then variation in condition could weaken selection on sexual signals. Conversely, if individuals in poor condition invest more in mating, say because they benefit more from finding a mate, then variation in condition could strengthen selection on sexual signals. Here we examined the effect of female condition on responsiveness to male mating signals – a key component of mating behavior – in the Pacific field cricket ( Teleogryllus oceanicus ). We manipulated female condition by rearing females on either a high- or low-quality diet. Although our diets generated substantial differences in adult body condition, the two groups of females had similar responsiveness to male mating signals. Our results suggest that, contrary to theoretical predictions, fitness-related behaviors do not always exhibit condition dependence.

Modulatory effects of bioactive natural compounds on pruritic pathways: mechanistic basis and therapeutic prospects - Wagih H. Marcus; Hassan A. Ruby; Amira E. Awwad; Mahrous H. Mahrous; Ebraheem Abouelwafa; Mohamed A. S. Badawy; Riham A. El-Shiekh; Eman S. Zaki; Mahmoud Abdelmouti Mahmoud (Inflammopharmacology, 2025)
Chronic pruritus, characterized by persistent itching, is a significant health issue that adversely affects individuals’ quality of life, particularly in palliative care environments. Conventional treatments frequently do not yield sufficient relief and may lead to undesirable side effects, which has spurred interest in exploring alternative therapeutic options. A thorough literature search was conducted across several databases such as PubMed, Web of Science, Scopus, and EKB, with an emphasis on studies involving in vitro, animal models, and clinical trials utilizing terms like “plant,” “extract,” and “pruritus.” All studies were considered regardless of their publication date and were limited to English-language articles. This review highlights the promise of various medicinal plants, including chamomile, Aloe vera , calendula, curcumin, lavender, licorice, and peppermint, as adjunctive therapies for pruritus. These plants possess a range of pharmacological properties, such as anti-inflammatory, antioxidant, and skin-soothing effects, which are relevant to the complex nature of pruritus. Their favorable safety profiles and natural origins enhance their appeal in holistic and patient-centered care models.

Exogenous Calcium Chloride and Chitosan Improved Postharvest Quality and Storability of Mango cv. ‘Mallika’ - Nishant Arya; Kumari Karuna; Ruby Rani; Abhay Mankar; Roopendra Kumar; Deepak Kumar (Applied Fruit Science, 2025)

A Systematic Review of Potential Health Risk Assessments for Nitrate Contamination in Different Water Resources in India - Ritu Ritu; Ruby Ruby; Dimple Dimple; Nancy Nancy; Arup Giri (Water, Air, & Soil Pollution, 2025)

Exploratory Analysis of Clearance Rates and Feeding Constraints in the Invasive Black Mussel Mytella strigata (Hanley, 1843) Across Salinity and Seston Gradients - Kaent Immanuel N. Uba; Robert Keith A. Sienes; Michael H. Flores; Hessed T. Cabanilla; Gaireen D. Gaid; Junaisah Nissi L. Degoma; Delyn M. Bucay; Ruby C. Gonzales (Estuaries and Coasts, 2025)

Two-stage Adaptive Modelling Framework for Long-term Monthly Operation of a Multi-purpose Reservoir for Regulating Environmental Flows - Ruby Jose; K. Srinivasan (Water Resources Management, 2025)

Metabarcoding reveals unique rhizospheric microbiomes of Rhizophora in Indian Mangroves - V. Kavi Sidharthan; Ruby Patel; Muthuprasad Thiyaharajan; Charishma Krishnappa; Swapnendu Pattanaik; Aundy Kumar (Folia Microbiologica, 2025)

Substrate stiffness dictates unique paths towards proliferative arrest in WI-38 cells - Alyssa M. Kaiser; Amirali Selahi; Wenjun Kong; J. Graham Ruby (GeroScience, 2025)
Finite replicative potential is a defining feature of non-transformed somatic cells, first established by Leonard Hayflick in vitro using WI-38 human lung fibroblasts. Once proliferative capacity is exhausted due to telomere shortening, cells enter into a state called replicative senescence, which can be avoided through ectopic expression of telomerase reverse transcriptase (hTERT). As WI-38 cells approach replicative arrest, molecular pathways linked to mechanotransduction are induced, including YAP signaling, but the potential interplay between replicative lifespan and the mechanical environment of the cell remains unexplored. Here, we investigate the influence of mechanosensation on the trajectory towards replicative arrest taken by WI-38 cells by growing cells on substrates of varying stiffnesses. Matrix softening slowed proliferation, altered cellular phenotypes, and shortened proliferative lifespan while hTERT expression abrogated or reduced these responses. Our analyses of bulk and single-cell RNA-sequencing and ATAC-sequencing revealed the emergence of a unique G1 transcriptional state on soft substrates, characterized by an AP-1 transcription factor program, which failed to manifest with hTERT expression. Together, these findings reveal how the mechanical environment alters WI-38 cell proliferative lifespan and dictates unique paths towards growth arrest.

Alkyl Chain-Tuned Fluorescent Sensors: Phenanthroimidazole Derivatives for Selective Detection of Nitroaromatic Compounds Containing Phenolic Group - Mohd Tameem; Abid Ali; Ruby Ahmed; Farman Ali; Nagmajahan; Musheer Ahmad (Journal of Fluorescence, 2025)

Characterization of a silver nanoparticle derived from the fruit peel of Myristica fragrans on mosquito control - Varghese Edwin Hillary; Murugeswaran Dayana Senthamarai; Thomas Jose Antony; Stanislaus Antony Ceasar; Muthuswami Ruby Rajan; Karthikeyan Jagannathan; Heba Talat Ebeed; Savarimuthu Ignacimuthu (International Journal of Tropical Insect Science, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Correction to: Rapid root development in clay subsoils enhances the early growth of native grassland species - Katherine Horsfall; Nicholas S. G. Williams; Ruby N. Michael; Stephen J. Livesley (Plant and Soil, 2025)

Assessing wheat responses to soil acidification and liming using hyperspectral imaging - Ruby Hume; Petra Marschner; Sean Mason; Rhiannon K. Schilling; Huajian Liu; Nathaniel Jewell; Christoper J. Brien; Luke M. Mosley (Plant and Soil, 2025)

Rapid root development in clay subsoils enhances the early growth of native grassland species - Katherine Horsfall; Nicholas S. G. Williams; Ruby N. Michael; Stephen J. Livesley (Plant and Soil, 2025)

What Kills Mature Street and Park Trees in Cities? Systematic Quantitative Review of Published Case Studies - Anna Petrova; Ruby Naomi Michael; Chris Pratt (Environmental Management, 2025)
Street and park trees often endure harsher conditions, including increased temperatures and drier soil and air, than those found in urban or natural forests. These conditions can lead to shorter lifespans and a greater vulnerability to dieback. This literature review aimed to identify confirmed causes of street and park tree dieback in urban areas from around the world. Peer-reviewed case studies related to urban tree decline were scanned for the words “urban”, “city”, “cities”, “tree*”, “decline”, “dieback”, “mortality”, and “survival”. From an initial pool of 1281 papers on Web of Science and 1489 on Scopus, 65 original peer-reviewed research papers were selected for detailed analysis. Out of all species reported to decline, 46 were native, while non-natives were represented by 35 species. The most commonly affected trees were Platanus, Fraxinus, Acer, and Ficus . Most studies were conducted in Mediterranean, humid subtropical, and humid continental climates, with the greatest representation from the United States, followed by Australia, Brazil, Iran, Italy, and Russia. Many authors focused on either biotic or abiotic causes of dieback; some explored both, and some also discussed underlying environmental and urban stresses as potential predisposing factors. The majority (81% of the papers) concluded that a decline was caused by either an arthropod or a microorganism. Overall, it was suggested that changing management strategies to improve water availability and soil health might help with tree resilience. Additionally, regular monitoring and research, along with improving tree species selection and implementing biological and chemical control methods, can help prevent or slow down tree decline. Increasing awareness and adopting preventative approaches could help to extend the lifespan of street and park trees in urban environments and mitigate some of the biological threats, especially considering the challenges we may be facing due to the changing climate.

Improved Simulation of East Asian Summer Monsoon in the High-resolution CESM1 and Its Causes - Yingshuo Xiang; Lu Dong; Fengfei Song; Lixin Wu; L. Ruby Leung; Shengpeng Wang; Enze Dong; Hong Wang (Advances in Atmospheric Sciences, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Exploring soil pedogenesis through frequency-dependent magnetic susceptibility in varied lithological environments - Abdessalam Ouallali; Naima Bouhsane; Saidati Bouhlassa; Velibor Spalevic; Shuraik Kader; Ruby Michael; Paul Sestras (Euro-Mediterranean Journal for Environmental Integration, 2025)
The use of percent frequency-dependent magnetic susceptibility (χfd%) is well-established for detecting superparamagnetic (SP) components in fine-grained soils and sediments. This study employs χfd% as a direct indicator of pedogenetic processes in soils from the Moroccan Rif region. Three soil transects (T1, T2, and T3), each comprising four soil cores with depths reaching 100 to 120 cm, were sampled from distinct lithological formations within an area subject to moderate to intense erosion. A total of 272 soil samples were collected and analyzed using MS2 Bartington Instruments, providing values to calculate χfd% and identify ultrafine ferrimagnetic minerals (SP, < 0.03 μm). In Quaternary fluvial terraces (T1) soils, approximately 60% of the samples indicate a mixture of SP, multidomain (MD), and Single Stable Domain (SSD) magnetic grains, while 30% contained coarser MD grains. Only 10% of the samples exhibit predominantly superparamagnetic (SP) grains. Soils on marly substrates (T2) showed 90% of samples with a combination of SP, MD, and SSD, and just 10% had SP grains. In contrast, soils from Villafranchian sandy deposits displayed χfd% values exceeding 10% in over 50% of samples, indicating that almost all iron components consist of SP grains. Physico-chemical analyses of the soils in profiles T1, T2, and T3 reveal distinct characteristics, including variations in clay content, organic matter, nutrient levels, and proportions of free and total iron. These results are important for understanding soil evolution and pedogenesis, with profiles T1 and T3 showing advanced development marked by high mineral iron, clay, and organic matter content. In contrast, profile T2 reflects a weak stage, influencing nutrient availability and contributing to overall soil dynamics in the respective profiles. The results of this study suggest that magnetic susceptibilities in these samples primarily originate from pedogenetic sources, revealing significantly advanced pedogenesis compared to T1 and T2 soils. The findings of this study align with previous research on soil erosion and degradation in the region, demonstrating that soils developed on terraces and marly substrates are more degraded and less stable than those on sandy substrates. This study underscores the utility of magnetic susceptibility as a rapid and effective indicator for initial soil assessment and gauging the degree of pedogenesis.

Projections of future climate for U.S. national assessments: past, present, future - Samantha Basile; Allison Crimmins; Fredric Lipschultz; Kenneth E. Kunkel; Kate Marvel; Adam Terando; Claudia Tebaldi; David Pierce; Wenying Su; L. Ruby Leung; Katharine Hayhoe (Climatic Change, 2025)

Mercury toxicity resulting from enzyme alterations- minireview - Ruby A. Ynalvez; Rene A. Rangel; Jose A. Gutierrez (BioMetals, 2025)

Classic Theory of Aerosol Filtration for Application to Urban Green Infrastructure - Nathalie Tomson; Ruby N. Michael; Igor E. Agranovski (Water, Air, & Soil Pollution, 2025)
The use of green infrastructure (GI) in urban environments has been widely investigated for its associated ecosystem services including air pollution mitigation. Plants are well-known for their ability of purifying air through photosynthesis and microbial activities occurring in the rhizosphere, however the simple filtration of particulate matter in air by plants is still not well understood. This study aimed to investigate the potential to adapt classic filtration theory for application in GI design. Two native Australian plants used as filter media were involved in laboratory experiments to remove aerosol particles ranging in size from 0.3 to > 10 µm. A comparison of aerosol removal efficiencies obtained from the laboratory experiments and predicted through classic filtration theory showed good correlation for the smaller (needle-like) leaf system. In contrast, the correlation obtained for a plant with larger elliptical leaves was not as good, showing a larger difference between the results. Such outcomes led to the conclusion that smaller and spatially homogeneous plant systems have more predictable aerosol filtration characteristics, which can be reasonably calculated using filtration theory. This finding provides practical insight into GI design, allowing quantitative predictions of local air pollution reductions using green barriers. Graphical Abstract

Theoretical studies on safety and efficacy of 16 small-molecule MC4R antagonists as therapeutics for obesity - Sravani Joshi; Ruby Srivastava (Journal of Proteins and Proteomics, 2025)

Peptide-Based Nanoparticles from Agricultural and Food Waste: Applications in Smart Food Packaging - Pooja yadav; Nishita Makkar; Muskan Jain; Ruby Prakash (International Journal of Peptide Research and Therapeutics, 2025)

Isotopic niche dynamics in populations of facultative amphidromous fish - Rodrigo Ramírez-Álvarez; Sergio Contreras; Ruby López-Rodríguez; Konrad Górski (Hydrobiologia, 2025)

Multi-Objective Modeling Framework for Environmental Flow Optimization in a River-Reservoir System Using Histogram Comparison Approach for Estimation of Hydrologic Alteration - Ruby Jose; Srinivasan K (Water Resources Management, 2025)

Benefits and burdens: perceiving the impact of non-indigenous black mussel (Mytella strigata) on ecosystem services and human well-being in Panguil Bay, Philippines - Kaent Immanuel N. Uba; Robert Keith A. Sienes; Hessed T. Cabanilla; Paz Geneveve Q. Gacus; Michael H. Flores; Ruby C. Gonzales; Junaisah Nissi L. Degoma; Delyn M. Bucay (Biological Invasions, 2025)

The tale of tapetum: from anther walls to pollen wall - Ruby Biswas; Shubho Chaudhuri (The Nucleus, 2024)

Two-Stage Polsar Scattering Model-Based Classification Scheme for Improved Glacier Facies Mapping - Ruby Panwar; Amit Kumar; Praveen Kumar (Journal of the Indian Society of Remote Sensing, 2024)

Predicting Soil Organic Carbon in Forest Soils of Telangana, India: A Comparative Analysis of Deterministic and Geostatistical Interpolation Models - Ruby Patel; Shaik Sharief; Sherline; Avinash Kodchire; Vijender Pal Panwar (Journal of Soil Science and Plant Nutrition, 2024)

AtHMGB15 regulates tapetal apoptosis in pollen development and actin dynamics during pollen germination in arabidopsis - Ruby Biswas; Shubho Chaudhuri (Plant Reproduction, 2024)

Seasonal delay of Sahelian rainfall driven by an east–west contrast in radiative forcing in idealized CESM experiments - Hongqiang Dong; Fengfei Song; Fukai Liu; Hai Wang; Lu Dong; L. Ruby Leung; Jian Lu (Climate Dynamics, 2024)

Effect of environmental air pollutants on placental function and pregnancy outcomes: a molecular insight - Sunil Singh; Isha Goel; Smita Tripathi; Ashok Ahirwar; Megha Kumar; Anubhuti Rana; Ruby Dhar; Subhradip Karmakar (Environmental Science and Pollution Research, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Patient Education Materials for Immobilisation Masks in Radiation Therapy for Adult Head and Neck Cancer Patients: A Scoping Review - Lucy Wood; Ruby Holman; Uyen Nguyen; Helen Nguyen; Aurora Senaratna; Misha Adams; Apajok Apath (Journal of Cancer Education, 2024)
Immobilisation masks (IMs) are used for people with head and neck cancer (HNC) undergoing radiation therapy (RT) treatment to ensure accuracy and reproducibility between treatments. Claustrophobia-related mask anxiety in HNC patients is common and can compromise treatment due to patient distress. This scoping review aimed to describe the content of publicly available Patient Education Materials (PEMs) for people with HNC undergoing RT. Three search engines (Bing, Yahoo, and Google) were systematically searched using standard terms. PEMs in audio-visual or written formats were eligible for inclusion if the target readership was adults with HNC and included content on IMs for RT. Content was appraised using the Patient Education Materials Assessment Tool for Printable and Audio-Visual Materials to assess understandability and actionability. In total, 304 PEMs were identified of which 20 met the inclusion criteria. Sixteen PEMs were webpages, three were PDF format, and one was a standalone video. The understandability and actionability of PEMs ranged between 47 to 100% and 0 to 80%, respectively. PEMs authored by Foundations/Organisations scored higher in understandability (80–100%) and were more likely to discuss mask anxiety coping strategies. In comparison, News sites and IM manufacturers published PEMs with the lowest understandability scores (20–80%). The significant variations in the quality of IM PEMs identified suggest that some sources may be more effective at informing patients about IMs. Although multiple aspects of the PEMs were consistent across the reviewed materials, many PEMs lacked information, and a stronger focus on understandability and actionability is required.

Synergistic neuromodulation therapy for persistent spinal pain: a proof-of-concept trial on the use of spinal cord and dorsal root ganglion stimulation - Augusto Müller Fiedler; Guilherme Santos Piedade; Bernardo Assumpção de Monaco; Ruby Rose Taylor; Michelle Dawn Williams; John L. Danny; Adrienne Minor; Joacir Graciolli Cordeiro (Acta Neurologica Belgica, 2024)

How the Resist-Accept-Direct framework is being used by communities for socio-economic climate adaptation: a case study in Australia’s Murray-Darling Basin - Ruby C. Olsson; Carina A. Wyborn; Lorrae E. van Kerkhoff (Regional Environmental Change, 2024)
Globally, water governance struggles to reconcile increased demands on water resources with climate change–induced reductions in supply, making climate adaptation in water governance a pressing concern. The Resist-Accept-Direct (RAD) framework has emerged as a climate adaptation tool designed to help make adaptation decisions. However, there is limited understanding of social and political factors, which are critical in driving RAD decisions. This paper explores how communities are employing RAD to make climate adaptation decisions, using a case study of the Goulburn-Murray Resilience Strategy (the Strategy); a community-led strategy that uses a version of the RAD framework to build regional resilience in the Goulburn-Murray Irrigation District (GMID) in Australia’s Murray-Darling Basin (MDB). The Strategy focuses on building socio-economic, rather than ecological, resilience, making this research a valuable contribution to RAD literature. To apply the RAD framework to socio-economic adaptation, we adapted the framework to include IPCC language around incremental, transformational, planned, and autonomous adaptation. With the GMID considered a leader of resilience thinking in Australia, the Strategy may help decision-makers address water overallocation and contested governance in the MDB, and provide lessons for water governance globally. Data analysed from 20 semi-structured interviews with people involved with the Strategy revealed two main findings: (1) Communities and governments prioritise different actions under the RAD framework. Governments, particularly at the state level, preference incremental planned adaptation to maintain the status quo (resist), over incremental autonomous adaptation to changing conditions (accept), and transformational planned adaptation at various scales (direct). (2) Community and government actors perceive that factors driving governments’ preference for incremental-resist adaptation include electoral short-termism, linear planning, and conservative government culture.

Spatiotemporal Shift of Soil Microbes in Conservation Agriculture under a Rice-Based Cropping System at the New Alluvial Zone of Lower Gangetic Plain - Puja Singh; Susanta Dutta; Siddhartha Mukherjee; Niharendu Saha; Bishnuprasad Dash; Samrat Ghosh; Biswabara Sahu; Ruby Pate; Ahana Dey; M Jaison; Tufleuddin Biswas; Biswapati Mandal (Journal of Soil Science and Plant Nutrition, 2024)

Immunomodulation and Humoral Immune Response in Teleost Immunized with Aeromonas-Derived Antigenic Extracellular Bioactive Molecules - Patrick Senam Kofi Fatsi; Koichiro Kawai; Ruby Asmah; Betty Bandoh Oppong; Ebenezer Koranteng Appiah; Shaharior Hashem; Acheampong Addo; Joyce Kplorla Kusorgbor; Emmanuel Kaboja Magna; Abraham Kusi Obeng; Lydia Quansah; Courage Kosi Setsoafia Saba; et al. (Indian Journal of Microbiology, 2024)

Seagrass cover and associated macrobenthic marine invertebrates in Southern Philippines - Dan Arriesgado; Elgen Arriesgado; Elnor Roa; Aida Perpetua; Ruby Gonzales; Rodrigo Acuña; Rustan Eballe; Delyn Bucay; Mayenne Balaba; Lyndon Roa; Bopp Benjack Janolino; Richard Muallil; et al. (Aquatic Ecology, 2024)

Sulfur mitigates lead toxicity through phytochelatin-driven vacuolar sequestration and antioxidant defense in mustard (Brassica juncea) - Ruby Bagchi; MD. Arifuzzaman; MD. Atikur Rahman; Ahmad Humayan Kabir; MD. Sarwar Parvez (Biologia, 2024)

The first ensemble of kilometer-scale simulations of a hydrological year over the third pole - Emily Collier; Nikolina Ban; Niklas Richter; Bodo Ahrens; Deliang Chen; Xingchao Chen; Hui-Wen Lai; Ruby Leung; Lu Li; Alzbeta Medvedova; Tinghai Ou; Praveen Kumar Pothapakula; et al. (Climate Dynamics, 2024)
An accurate understanding of the current and future water cycle over the Third Pole is of great societal importance, given the role this region plays as a water tower for densely populated areas downstream. An emerging and promising approach for skillful climate assessments over regions of complex terrain is kilometer-scale climate modeling. As a foundational step towards such simulations over the Third Pole, we present a multi-model and multi-physics ensemble of kilometer-scale regional simulations for the hydrological year of October 2019 to September 2020. The ensemble consists of 13 simulations performed by an international consortium of 10 research groups, configured with a horizontal grid spacing ranging from 2.2 to 4 km covering all of the Third Pole region. These simulations are driven by ERA5 and are part of a Coordinated Regional Climate Downscaling EXperiment Flagship Pilot Study on Convection-Permitting Third Pole. The simulations are compared against available gridded and in-situ observations and remote-sensing data, to assess the performance and spread of the model ensemble compared to the driving reanalysis during the cold and warm seasons. Although ensemble evaluation is hindered by large differences between the gridded precipitation datasets used as a reference over this region, we show that the ensemble improves on many warm-season precipitation metrics compared with ERA5, including most wet-day and hour statistics, and also adds value in the representation of wet spells in both seasons. As such, the ensemble will provide an invaluable resource for future improvements in the process understanding of the hydroclimate of this remote but important region.

Current Trends and Innovative Approaches in Cancer Immunotherapy - Jaechang Kim; Ruby Maharjan; Jonghyuck Park (AAPS PharmSciTech, 2024)

Using mid-infrared spectroscopy as a tool to monitor responses of acidic soil properties to liming: case study from a dryland agricultural soil trial site in South Australia - Ruby Hume; Petra Marschner; Sean Mason; Rhiannon K. Schilling; Luke M. Mosley (Precision Agriculture, 2024)
Soil acidification is an issue for agriculture that requires effective management, typically in the form of lime (calcium carbonate, CaCO 3 ), application. Mid infrared (MIR) spectroscopy methods offer an alternative to conventional laboratory methods, that may enable cost-effective and improved measurement of soil acidity and responses to liming, including detection of small–scale heterogeneity through the profile. Properties of an acidic soil following lime application were measured using both MIR spectroscopy with Partial Least Squares Regression (MIR-PLSR) and laboratory measurements to (a) compare the ability of each method to detect lime treatment effects on acidic soil, and (b) assess effects of the different treatments on selected soil properties. Soil properties including soil pH (in H 2 O and CaCl 2 ), Aluminium (Al, exchangeable and extractable), cation exchange capacity (CEC) and organic carbon (OC) were measured at a single field trial receiving lime treatments differing in rate, source and incorporation. Model performance of MIR-PLSR prediction of the soil properties ranged from R 2 = 0.582, RMSE = 2.023, RPIQ = 2.921 for Al (extractable) to R 2 = 0.881, RMSE = 0.192, RPIQ = 5.729 for OC. MIR-PLSR predictions for pH (in H 2 O and CaCl 2 ) were R 2 = 0.739, RMSE = 0.287, RPIQ = 2.230 and R 2 = 0.788, RMSE = 0.311, RPIQ = 1.897 respectively, and could detect a similar treatment effect compared to laboratory measurements. Treatment effects were not detected for MIR-PLSR-predicted values of CEC and both exchangeable and extractable Al. Findings support MIR-PLSR as a method of measuring soil pH to monitor effects of liming treatments on acidic soil to help inform precision agricultural management strategies, but suggests that some nuance and important information about treatment effects of lime on CEC and Al may be lost. Improvements to prediction model performance should be made to realise the full potential of this approach.

Mathematical vs. machine learning models for particle size distribution in fragile soils of North-Western Himalayas - Owais Bashir; Shabir Ahmad Bangroo; Shahid Shuja Shafai; Tajamul Islam Shah; Shuraik Kader; Lizny Jaufer; Nicola Senesi; Alban Kuriqi; Negar Omidvar; Soora Naresh Kumar; Ayyanadar Arunachalam; Ruby Michael; et al. (Journal of Soils and Sediments, 2024)
Purpose Particle size distribution (PSD) assessment, which affects all physical, chemical, biological, mineralogical, and geological properties of soil, is crucial for maintaining soil sustainability. It plays a vital role in ensuring appropriate land use, fertilizer management, crop selection, and conservation practices, especially in fragile soils such as those of the North-Western Himalayas. Materials and methods In this study, the performance of eleven mathematical and three Machine Learning (ML) models used in the past was compared to investigate PSD modeling of different soils from the North-Western Himalayan region, considering that an appropriate model must fit all PSD data. Results and discussion Our study focuses on the significance of evaluating the goodness of fit in particle size distribution modeling using the coefficient of determination (R 2 adj = 0.79 to 0.45), the Akaike information criterion (AIC = 67 to 184), and the root mean square error (RMSE = 0.01 to 0.09). The Fredlund, Weibull, and Rosin Rammler models exhibited the best fit for all samples, while the performance of the Gompertz, S-Curve, and Van Genutchen models was poor. Of the three ML models tested, the Random Forest model performed the best (R 2 = 0.99), and the SVM model was the lowest (R 2 = 0.95). Thus, the PSD of the soil can be best predicted by ML approaches, especially by the Random Forest model. Conclusion The Fredlund model exhibited the best fit among mathematical models while random forest performed best among the machine learning models. As the number of parameters in the model increased better was the accuracy.

Five years later, with double the demographic data, naked mole-rat mortality rates continue to defy Gompertzian laws by not increasing with age - J. Graham Ruby; Megan Smith; Rochelle Buffenstein (GeroScience, 2024)
The naked mole-rat ( Heterocephalus glaber ) is a mouse-sized rodent species, notable for its eusociality and long lifespan. Previously, we reported that demographic aging, i.e., the exponential increase of mortality hazard that accompanies advancing age in mammals and other organisms, does not occur in naked mole-rats (Ruby et al., 2018), a finding that has potential implications for human healthy aging. The demographic data supporting that conclusion had taken over three decades to accumulate, starting with the original rearing of H. glaber in captivity. This finding was controversial since many of the animals in that study were relatively young. In the 5 years following that study, we have doubled our quantity of demographic data. Here, we re-evaluated our prior conclusions in light of these new data and found them to be not only supported but indeed strengthened. We additionally provided insight into the social dynamics of captive H. glaber with data and analyses of body weight and colony size versus mortality. Finally, we provide a phylogenetically proximal comparator in the form of lifespan data from our Damaraland mole-rat ( Fukomys damarensis ) colony and demographic meta-analysis of those data along with published data from Ansell’s mole-rat ( Fukomys anselli ). We found Fukomys mortality hazard to increase gradually with age, an observation with inferences on the evolution of exceptional lifespan among mole-rats and the ecological factors that may have accompanied that evolution.

Characterization and variability of morpho-genetic traits of commercial importance in achiote collection - Rodolfo Pech-Hoil; Miriam Monserrat Ferrer; Margarita Aguilar-Espinosa; June Simpson; Ruby Valdez-Ojeda; Adolfo Guzmán-Antonio; Luis Carlos Gutiérrez-Pacheco; Renata Rivera-Madrid (New Forests, 2024)

Applications and advancements of nanoparticle-based drug delivery in alleviating lung cancer and chronic obstructive pulmonary disease - Gabriele De Rubis; Keshav Raj Paudel; Leander Corrie; Samir Mehndiratta; Vyoma K. Patel; Popat S. Kumbhar; Arehalli Sidramappa Manjappa; John Disouza; Vandana Patravale; Gaurav Gupta; Bikash Manandhar; Rashi Rajput; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Biotechnological strategies to decipher the functions of abiotic stress-associated genes in soybean - Ruby Tiwari; Manchikatla V. Rajam (Plant Biotechnology Reports, 2024)

Investigating the levels of organochlorine pesticides in human milk at three lactational stages: an intensive Ghanaian study - Justice Wiston Amstrong Jonathan; Daniel Elorm Kwame Kabotso; David Kofi Essumang; John Kwesi Bentum; Innocentia Ruby Gborgblorvor; Fidelis M. Kpodo; Francis Ofosu-Koranteng; Comfort Worna Lotse; Norkplim Dei Hlorlewu (Environmental Monitoring and Assessment, 2024)

Region and cloud regime dependence of parametric sensitivity in E3SM atmosphere model - Yun Qian; Zhun Guo; Vincent E. Larson; L. Ruby Leung; Wuyin Lin; Po-Lun Ma; Hui Wan; Hailong Wang; Heng Xiao; Shaocheng Xie; Ben Yang; Kai Zhang; et al. (Climate Dynamics, 2024)
The Department of Energy (DOE)’s Energy Exascale Earth System Model (E3SM), including its atmosphere model (EAM), has many relatively new features. In a previous study we conducted a systematic parametric sensitivity analysis for EAM based on short, perturbed parameter ensemble (PPE) simulations, mainly focusing on global mean climate features and metrics. While parameter values in global climate models are generally invariant in space and time, model response to parameters perturbation may vary by regions and climate regimes, which motivates the need to better understand the EAM model behaviors and physics at regional scale and process level. In this study, using the same set of PPE simulations and a similar sensitivity analysis framework, we identify parameters that cause largest sensitivities over different regions and compare model responses in fast atmospheric processes to the parameters across different cloud regimes for several important cloud-related fidelity metrics. We find that cloud forcing has opposite response to some parameters over mid-latitude vs. tropical land. We also analyze how the parametric sensitivity varies as stratocumulus transitions to shallow convection and to deep convection over ocean. Low cloud forcing and shortwave cloud forcing in the subtropical eastern Pacific are most sensitive to the parameters controlling the width of the probability density function (PDF) of the subgrid vertical velocity ( w’ ) ( gamma ) and the damping of the w’ skewness ( c8 ) near the coast but become more sensitive to the parameter affecting the damping of the w’ variance ( c1 ) further offshore. Detailed interpretation of the spatial dependence of parametric sensitivity is provided. We also investigate how the parametric sensitivity evolves with prediction duration. This study improves our process-level understanding of cloud physics and parameterization and provides insights for developing more advanced regime-aware parameterization schemes in global climate model.

Acute Toxicity, Hematological Profile, and Histopathological Effects of MgO Nanoparticles on Gills, Muscle, Liver of Mrigal, Cirrhinus mrigala - Shanmugam Sudhabose; Balakrishnan Sooryakanth; Muthuswami Ruby Rajan (Biological Trace Element Research, 2024)

A new method for predicting hurricane rapid intensification based on co-occurring environmental parameters - Anushka Narayanan; Karthik Balaguru; Wenwei Xu; L. Ruby Leung (Natural Hazards, 2024)
Tropical cyclones (TCs) that undergo Rapid Intensification (RI) can pose serious socioeconomic threats and can potentially result in major damaging impacts along coastal areas. Considering the complexity of various physical mechanisms that play a role in RI and its relatively low probability of occurrence, predicting RI remains a major operational challenge. In this study, we propose a simple deterministic binary classification model based on the co-occurrence of environmental parameters (MCE) to predict an RI event. More specifically, the model determines the possibility of RI based on a simple count of the number of environmental predictors deemed favorable and unfavorable. We compare our model results to logistic regression (LR) and decision tree (DT) models, well-trained using the same set of environmental predictors. Results reveal that at an RI threshold of 30 kt, the MCE exhibits a critical success index score of 0.233 which is 14% higher than DT and LR model performances. When tested at multiple RI thresholds, the MCE displays relatively higher skill scores across multiple metrics. By simultaneously evaluating the favorability of predictors, the MCE is able to comparatively reduce the number of false alarms predicted when certain predictors are unfavorable toward RI. Interpreting these model results to gain a physical understanding of how co-occurring environmental parameters can affect RI, we highlight future directions for using models based on the MCE approach to understand and predict TC RI as well as other meteorological extremes.

One-way coupling of E3SM with ADCIRC demonstrated on Hurricane Harvey - Benjamin Pachev; L. Ruby Leung; Tian Zhou; Clint Dawson (Natural Hazards, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Tropical cyclone strength, precipitation, and environment in variable resolution CAM-MPAS simulations over Western North Pacific - Yuan Liang; Ben Yang; Minghuai Wang; Yipeng Guo; Koichi Sakaguchi; L. Ruby Leung (Climate Dynamics, 2023)

Atmospheric Microplastics: Perspectives on Origin, Abundances, Ecological and Health Risks - Shivali Gupta; Rakesh Kumar; Akanksha Rajput; Ruby Gorka; Antima Gupta; Nazuk Bhasin; Sudesh Yadav; Anju Verma; Kirpa Ram; Madulika Bhagat (Environmental Science and Pollution Research, 2023)

Overexpression of flowering locus D (FLD) in Indian mustard (Brassica juncea) enhances tolerance to Alternaria brassicae and Sclerotinia sclerotiorum - Shashi Shekhar; Ruby Panwar; Subhash Chandra Prasad; Deepak Kumar; Anjana Rustagi (Plant Cell Reports, 2023)

Effects of herbicides and mulch on the soil carbon, nitrogen, and microbial composition of two revegetated riparian zones over 3 years - Negar Omidvar; Steven M. Ogbourne; Zhihong Xu; Joanne Burton; Rebecca Ford; Babak Salehin; Iman Tahmasbian; Ruby Michael; Rachele Wilson; Shahla Hosseini Bai (Journal of Soils and Sediments, 2023)
Purpose Revegetation of riparian zones is important to improve their soil nitrogen (N) dynamics and to preserve their microbial compositions. However, the success of revegetation projects currently depends on weed control to reduce non-target vegetation competing over nutrients and to ensure the target plant species growth and survival. Different weed control methods affect soil microbial composition and N cycling. However, the long-term effects of herbicides on soil nitrogen (N) pools and microbial community composition remain uncertain even after cessation of the herbicide application. Materials and methods This study compared the impacts of different herbicides (Roundup ® , BioWeed™, Slasher ® , and acetic acid) with mulch on soil N dynamics and microbial community structure 3 years after vegetation establishment (herbicides applied repeatedly in the first 2 years after which no herbicides were applied in the third final year). Results and discussion Soil microbial biomass carbon (MBC) was significantly higher in mulch compared with Roundup ® , BioWeed™, Slasher ® , and acetic acid at month 26 at the Kandanga site and month 10 at the Pinbarren site. Soil MBC remained significantly higher in mulch compared with Roundup ® and BioWeed™, 12 months after the cessation of herbicide application at the Pinbarren site. Soil MBC in the Roundup ® and BioWeed™ groups was also lower than the acceptable threshold (160 mg kg −1 ) at month 34 at the Pinbarren site. Soil NO 3 − -N was significantly higher in the mulch than the Roundup ® at months 22 and 34 after revegetation at the Pinbarren site which could be partly explained by the decreased abundance of the denitrifying bacteria ( Candidatus solibacter and C. koribacter ). Additionally, both soil bacterial and fungal communities at the Pinbarren site and only fungal community at the Kandanga site were different in the mulch group compared with all other herbicides. The differences persisted 12 months after the cessation of herbicide application at the Pinbarren site. Conclusion Our study suggested that the application of mulch to assist with riparian revegetation would be beneficial for soil microbial functionality. The use of herbicides may have long-lasting effects on soil microbial biomass and diversity and therefore herbicides should be used with caution as part of an integrated land management plan.

Effectiveness of Non-Pharmacological Interventions for Agitation during Post-Traumatic Amnesia following Traumatic Brain Injury: A Systematic Review - Sarah L. Carrier; Jennie Ponsford; Ruby K. Phyland; Amelia J. Hicks; Adam McKay (Neuropsychology Review, 2023)
Agitation is common in the early recovery period following traumatic brain injury (TBI), known as post-traumatic amnesia (PTA). Non-pharmacological interventions are frequently used to manage agitation, yet their efficacy is largely unknown. This systematic review aims to synthesize current evidence on the effectiveness of non-pharmacological interventions for agitation during PTA in adults with TBI. Key databases searched included MEDLINE Ovid SP interface, PubMed, CINAHL, Excerpta Medica Database, PsycINFO and CENTRAL, with additional online reviewing of key journals and clinical trial registries to identify published or unpublished studies up to May 2020. Eligible studies included participants aged 16 years and older, showing agitated behaviours during PTA. Any non-pharmacological interventions for reducing agitation were considered, with any comparator accepted. Eligible studies were critically appraised for methodological quality using Joanna Briggs Institute Critical Appraisal Instruments and findings were reported in narrative form. Twelve studies were included in the review: two randomized cross-over trials, three quasi-experimental studies, four cases series and three case reports. Non-pharmacological interventions were music therapy, behavioural strategies and environmental modifications, physical restraints and electroconvulsive therapy. Key methodological concerns included absence of a control group, a lack of formalised agitation measurement and inconsistent concomitant use of pharmacology. Interventions involving music therapy had the highest level of evidence, although study quality was generally low to moderate. Further research is needed to evaluate non-pharmacological interventions for reducing agitation during PTA after TBI. Systematic review registration number: PROSPERO (CRD42020186802), registered May 2020.

Improved and reliable plant regeneration and Agrobacterium-mediated genetic transformation in soybean (Glycine max L.) - Ruby Tiwari; Ajay K. Singh; Manchikatla V. Rajam (Journal of Crop Science and Biotechnology, 2023)

Towards Ensemble-Based Kilometer-Scale Climate Simulations over the Third Pole Region - Andreas F. Prein; Nikolina Ban; Tinghai Ou; Jianping Tang; Koichi Sakaguchi; Emily Collier; Sanjay Jayanarayanan; Lu Li; Stefan Sobolowski; Xingchao Chen; Xu Zhou; Hui-Wen Lai; et al. (Climate Dynamics, 2023)

Comparison of efficiency of various DC-DC converters connected to solar photovoltaic module - Krishnaraj Nisha; Ruby Beniwal (Environmental Science and Pollution Research, 2023)

Cuscuta reflexa Possess Potent Inhibitory Activity Against Human Malaria Parasite: An In Vitro and In Vivo Study - Sashi Bhusan Ojha; Raj Kumar Sah; Evanka Madan; Ruby Bansal; Shaktirekha Roy; Shailja Singh; Gunanidhi Dhangadamajhi (Current Microbiology, 2023)

Comprehensive Analysis of the Physiological Characterization of Escherichia coli Nissle 1917 - S. Ramadevi; Ruby Shelin; Meenakshi Shanmugaraja (Current Microbiology, 2023)

Remarkable photocatalytic performances towards pollutant degradation under sunlight and enhanced electrochemical properties of TiO2/polymer nanohybrids - Mariadhas Jarvin; Daniel Rani Rosaline; Thamizharasan Gopalakrishnan; Maniveldoss Beaula Ruby Kamalam; Edson Luiz Foletto; Guilherme Luiz Dotto; Savariroyan Stephen Rajkumar Inbanathan (Environmental Science and Pollution Research, 2023)

Soil Selenium Addition for Producing Se-Rich Quinoa and Alleviating Water Deficit on the Peruvian Coast - Ruby Vega-Ravello; Maria Belen Romero-Poma; Cynthia de Oliveira; Luiz Roberto Guimarães Guilherme; Guilherme Lopes (Journal of Soil Science and Plant Nutrition, 2023)

Correction to: Urbanization Impact on Regional Climate and Extreme Weather: Current Understanding, Uncertainties, and Future Research Directions - Yun Qian; T. C. Chakraborty; Jianfeng Li; Dan Li; Cenlin He; Chandan Sarangi; Fei Chen; Xuchao Yang; L. Ruby Leung (Advances in Atmospheric Sciences, 2023)
The article “Urbanization Impact on Regional Climate and Extreme Weather: Current Understanding, Uncertainties, and Future Research Directions”, written by Yun QIAN, TC CHAKRABORTY, Jianfeng LI, Dan LI, Cenlin HE, Chandan SARANGI, Fei CHEN, Xuchao YANG, and L. Ruby LEUNG was originally published electronically on the publisher’s internet portal on 25 of January 2022 with open access. With the author(s)’ decision, the copyright of the article changed from © The Author(s) 2022 to © Battelle Memorial Institute [2022]. The original article has been corrected.

Smart photovoltaic system for Indian smart cities: a cost analysis - Ruby Beniwal; Shruti Kalra; Narendra SinghBeniwal; Hari Om Gupta (Environmental Science and Pollution Research, 2023)

Classification of glacier with supervised approaches using PolSAR data - Ruby Panwar; Gulab Singh (Environmental Monitoring and Assessment, 2023)

RNA- and miRNA-interference to enhance abiotic stress tolerance in plants - Ruby Tiwari; Manchikatla Venkat Rajam (Journal of Plant Biochemistry and Biotechnology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Analysis of positive correlation in magnitude and time measurement for earthquake using electric signals - Oumaima Saidani; Ramkumar Raja Manoharan; Ahmed Samir Naje; Ruby Mishra; Arjun Subburaj; Maheswari S; Mohamed Yacin Sikkandar; Sankar Ganesh Sundaram; Regin Rajan; Sudhakar Sengan (Earth Science Informatics, 2022)

Antimicrobial, antioxidant, antiviral activity, and gas chromatographic analysis of Varanus griseus oil extracts - Shakeel Ahmad; Tahira Ruby; Mirza Imran Shahzad; Gildardo Rivera; Diana Victoria Navarrete Carriola; Aleem Ahmed Khan (Archives of Microbiology, 2022)

Detecting genetic epistasis by differential departure from independence - Ruby Sharma; Zeinab Sadeghian Tehrani; Sajal Kumar; Mingzhou Song (Molecular Genetics and Genomics, 2022)

Integrated Nutrient Management in Coconut (Cocos nucifera L.): an Assessment of Soil Chemical and Biological Parameters Under Subtropical Humid Climate - Deepak Kumar; Rajiv Rakshit; Ruby Rani; Pallavi Bharti; Anupam Das; Manoj Kundu (Journal of Soil Science and Plant Nutrition, 2022)

Enhancement of output power of semitransparent photovoltaic thermal air collector using ANFIS model - Ruby Beniwal; Narendra Singh Beniwal; Hari Om Gupta (Environmental Science and Pollution Research, 2022)

Urbanization Impact on Regional Climate and Extreme Weather: Current Understanding, Uncertainties, and Future Research Directions - Yun Qian; T. C. Chakraborty; Jianfeng Li; Dan Li; Cenlin He; Chandan Sarangi; Fei Chen; Xuchao Yang; L. Ruby Leung (Advances in Atmospheric Sciences, 2022)
Urban environments lie at the confluence of social, cultural, and economic activities and have unique biophysical characteristics due to continued infrastructure development that generally replaces natural landscapes with built-up structures. The vast majority of studies on urban perturbation of local weather and climate have been centered on the urban heat island (UHI) effect, referring to the higher temperature in cities compared to their natural surroundings. Besides the UHI effect and heat waves, urbanization also impacts atmospheric moisture, wind, boundary layer structure, cloud formation, dispersion of air pollutants, precipitation, and storms. In this review article, we first introduce the datasets and methods used in studying urban areas and their impacts through both observation and modeling and then summarize the scientific insights on the impact of urbanization on various aspects of regional climate and extreme weather based on more than 500 studies. We also highlight the major research gaps and challenges in our understanding of the impacts of urbanization and provide our perspective and recommendations for future research priorities and directions.

First report of fruit rot of jackfruit caused by Athelia rolfsii in India - Abdulmajeed Sajeena; Deepu Mathew; Jacob John; M. K. Dhanya; K. Sushitha; P. Ruby Nahan (Journal of Plant Pathology, 2022)

A comprehensive review of dye-sensitized solar cell optimal fabrication conditions, natural dye selection, and application-based future perspectives - Ruby Baby; Peter Daniel Nixon; Nallapaneni Manoj Kumar; M. S. P. Subathra; Nallamuthu Ananthi (Environmental Science and Pollution Research, 2022)

Biochemical and anti-inflammatory effect of Ocimum americanum Linn. extracts on gentamicin- and cisplatin-induced nephrotoxicity in rats - Christopher Larbie; Ruby A. Nyarko; Ademola A. Oyagbemi; Theophilus A. Jarikre; Clement O. Adjei; Emmanuel B. Aseidu; Rosemond Mawuenyega; Benjamin O. Emikpe (Advances in Traditional Medicine, 2021)

RNA interference and crop protection against biotic stresses - Ranjeet Kaur; Aparajita Choudhury; Sambhavana Chauhan; Arundhati Ghosh; Ruby Tiwari; Manchikatla Venkat Rajam (Physiology and Molecular Biology of Plants, 2021)

Evolution of CP2 transcription factors in Hexapoda - Matan Shelomi; Tuan Zea Tan; Ruby Yun-Ju Huang (Journal of Genetics, 2021)

Inter-laboratory automation of the in vitro micronucleus assay using imaging flow cytometry and deep learning - John W. Wills; Jatin R. Verma; Benjamin J. Rees; Danielle S. G. Harte; Qiellor Haxhiraj; Claire M. Barnes; Rachel Barnes; Matthew A. Rodrigues; Minh Doan; Andrew Filby; Rachel E. Hewitt; Catherine A. Thornton; et al. (Archives of Toxicology, 2021)
The in vitro micronucleus assay is a globally significant method for DNA damage quantification used for regulatory compound safety testing in addition to inter-individual monitoring of environmental, lifestyle and occupational factors. However, it relies on time-consuming and user-subjective manual scoring. Here we show that imaging flow cytometry and deep learning image classification represents a capable platform for automated, inter-laboratory operation. Images were captured for the cytokinesis-block micronucleus (CBMN) assay across three laboratories using methyl methanesulphonate (1.25–5.0 μg/mL) and/or carbendazim (0.8–1.6 μg/mL) exposures to TK6 cells. Human-scored image sets were assembled and used to train and test the classification abilities of the “DeepFlow” neural network in both intra- and inter-laboratory contexts. Harnessing image diversity across laboratories yielded a network able to score unseen data from an entirely new laboratory without any user configuration. Image classification accuracies of 98%, 95%, 82% and 85% were achieved for ‘mononucleates’, ‘binucleates’, ‘mononucleates with MN’ and ‘binucleates with MN’, respectively. Successful classifications of ‘trinucleates’ (90%) and ‘tetranucleates’ (88%) in addition to ‘other or unscorable’ phenotypes (96%) were also achieved. Attempts to classify extremely rare, tri- and tetranucleated cells with micronuclei into their own categories were less successful (≤ 57%). Benchmark dose analyses of human or automatically scored micronucleus frequency data yielded quantitation of the same equipotent concentration regardless of scoring method. We conclude that this automated approach offers significant potential to broaden the practical utility of the CBMN method across industry, research and clinical domains. We share our strategy using openly-accessible frameworks.

Outdoor/Indoor Contaminant Transport by Atmospheric Dust and Aerosol at an Active Smelter Site - Tania B. Rodríguez-Chávez; Kyle P. Rine; Reman M. Almusawi; Ruby O’Brien-Metzger; Mónica Ramírez-Andreotta; Eric A. Betterton; A. Eduardo Sáez (Water, Air, & Soil Pollution, 2021)

Exercise in the heat blunts improvements in aerobic power - Dustin Slivka; Robert Shute; Walter Hailes; Katherine Marshall; Megan Opichka; Halee Schnitzler; Brent Ruby (European Journal of Applied Physiology, 2021)

Efficacy and tolerability of brivaracetam in patients with intellectual disability and epilepsy - Ruby M. E. Gillis; Elisabeth A. Wammes-van der Heijden; Helenius J. Schelhaas; In Y. Tan; Dederieke A. M. Festen; Marian H. J. M. Majoie (Acta Neurologica Belgica, 2021)

Palaeoclimate estimates based on the late Miocene to early Pleistocene wood flora of the Bengal Basin: an insight into the climatic evolution of southern Asia - Ruby Ghosh; Anwesha Biswas; Angela A. Bruch; Torsten Utescher; Illora Sen; Dipak Kumar Paruya; Anupam Guha; Sultan-Ul-Islam; Subir Bera (Palaeobiodiversity and Palaeoenvironments, 2021)

Effect of Media Composition and Culture Time on the Lipid Profile of the Green Microalga Coelastrum sp. and Its Suitability for Biofuel Production - Ruby Alejandra Valdez-Ojeda; Maria Guadalupe del Rayo Serrano-Vázquez; Tanit Toledano-Thompson; Juan Carlos Chavarría-Hernández; Luis Felipe Barahona-Pérez (BioEnergy Research, 2021)

Establishment of a Cre-rat resource for creating conditional and physiological relevant models of human diseases - Huimin Zhang; Qi Zheng; Ruby Yanru Chen-Tsai (Transgenic Research, 2021)
The goal of this study is to establish a Cre/loxP rat resource for conditional and physiologically predictive rat models of human diseases. The laboratory rat ( R . norvegicus ) is a central experimental animal in several fields of biomedical research, such as cardiovascular diseases, aging, infectious diseases, autoimmunity, cancer models, transplantation biology, inflammation, cancer risk assessment, industrial toxicology, pharmacology, behavioral and addiction studies, and neurobiology. Up till recently, the ability of creating genetically modified rats has been limited compared to that in the mouse mainly due to lack of genetic manipulation tools and technologies in the rat. Recent advances in nucleases, such as CRISPR/Cas9 (clustered regularly-interspaced short palindromic repeats/CRISPR associated protein 9), as well as TARGATT™ integrase system enables fast, efficient and site-specific introduction of exogenous genetic elements into the rat genome. Here, we report the generation of a collection of tissue-specific, inducible transgenic Cre rats as tool models using TARGATT™, CRISPR/Cas9 and random transgenic approach. More specifically, we generated Cre driver rat models that allow controlled gene expression or knockout (conditional models) both temporally and spatially through the Cre-ERT2/loxP system. A total of 10 Cre rat lines and one Cre reporter/test line were generated, including eight (8) Cre lines for neural specific and two (2) lines for cardiovascular specific Cre expression. All of these lines have been deposited with the Rat Resource and Research Center and provide a much-needed resource for the bio-medical community who employ rat models for their studies of human diseases.

In situ river experiments to explore variability in Microcoleus autumnalis mat expansion - Georgia Thomson-Laing; Niamh Dyer; Ruby Whyte-Wilding; Susanna A. Wood (Hydrobiologia, 2021)

The role of international regimes and courts in clarifying prevention of harm in freshwater and marine environmental protection - Ruby Moynihan; Bjørn-Oliver Magsig (International Environmental Agreements: Politics, Law and Economics, 2020)

Efficient production of fatty acid methyl esters by a wastewater-isolated microalgae-yeast co-culture - Jessica K. Suastes-Rivas; Raúl Hernández-Altamirano; Violeta Y. Mena-Cervantes; Ruby Valdez-Ojeda; Tanit Toledano-Thompson; Luis R. Tovar-Gálvez; Silvia López-Adrián; Isaac Chairez (Environmental Science and Pollution Research, 2020)

Transcatheter Mitral Valve Replacement: State of the Art - Dylan Goode; Ruby Dhaliwal; Hadi Mohammadi (Cardiovascular Engineering and Technology, 2020)

Males and females exhibit similar muscle glycogen recovery with varied recovery food sources - Shannon Flynn; Alejandro Rosales; Walter Hailes; Brent Ruby (European Journal of Applied Physiology, 2020)
Purpose Research has elucidated the impact of post-exercise carbohydrate nutrition and environmental conditions on muscle glycogen re-synthesis. However, research has minimally considered the implications of glycogen recovery in females and has mostly focused on commercial sport nutrition products. The purpose of this study was to determine the effects of varied mixed macronutrient feedings on glycogen recovery and subsequent exercise performance in both sexes. Methods Males ( n = 8) and females ( n = 8) participated in a crossover study. Subjects completed a 90-min cycling glycogen depletion trial, then rested for 4 h. Two carbohydrate feedings (1.6 g kg −1 ) of either sport supplements or potato-based products were delivered at 0 and 2 h post-exercise. Muscle biopsies (glycogen) and blood samples (glucose, insulin) were collected during the recovery. Afterwards, subjects completed a 20 km cycling time trial. Results There was no difference between sexes or trials for glycogen recovery rates (male: 7.9 ± 2.7, female: 8.2 ± 2.7, potato-based: 8.0 ± 2.5, sport supplement: 8.1 ± 3.1 mM kg wet wt −1 h −1 , p > 0.05). Time trial performance was not different between diets (38.3 ± 4.4 and 37.8 ± 3.9 min for potato and sport supplement, respectively, p > 0.05). Conclusions These results indicate that food items, such as potato-based products, can be as effective as commercially marketed sports supplements when developing glycogen recovery oriented menus and that absolute carbohydrate dose feedings (g kg −1 ) can be effectively applied to both males and females.

Structural changes and variability of the ITCZ induced by radiation–cloud–convection–circulation interactions: inferences from the Goddard Multi-scale Modeling Framework (GMMF) experiments - William K. M. Lau; Kyu-Myong Kim; Jiun-Dar Chern; W. K. Tao; L. Ruby Leung (Climate Dynamics, 2020)
In this paper, we have investigated the impact of radiation–cloud–convection–circulation interaction (RC3I) on structural changes and variability of the Inter-tropical Convergence Zone (ITCZ) using the Goddard Multi-scale Modeling Framework, where cloud processes are super-parameterized, i.e., explicitly resolved with 2-D cloud resolving models embedded in each coarse grid of the host Goddard Earth Observing System-Version 5 global climate model. Experiments have been conducted under prescribed sea surface temperature conditions for 10 years (2007–2016), with and without cloud radiation feedback in the atmosphere, respectively. Diagnostic analyses separately for January and July show that RC3I leads to an enhanced and expanded Hadley Circulation characterized by (1) a quasi-uniform warming and moistening of the tropical atmosphere and a sharpening of the ITCZ with enhanced deep convection, more intense precipitation and higher clouds, (2) extended drying of the tropical marginal convective zones, and extratropical mid- to lower troposphere, and (3) a cooling of the polar regions, with increased baroclinicity and midlatitude storm track activities. Computations based on the zonal mean thermodynamic energy balance equation show that the radiative warming and cooling are strongly balanced by local adiabatic processes associated with changes in large-scale vertical motions, as well as horizontal atmospheric heat transport. In the tropics, enhanced short-wave absorption and longwave water vapor greenhouse effects by high clouds play key roles in providing strong positive feedback to the tropospheric warming. In the extratropics, increased atmospheric heat transport associated with changes in the Hadley circulation is balanced by strong longwave cooling above, and warming below due to increased high clouds. We also find a strong positive correlation between daily and pentad heavy rain in the ITCZ core, and expansion of the drier zones coupled to a contraction of the highly convective zones in the ITCZ, indicating a strong tendency RC3I-induced convective aggregation in tropical clouds i.e., wet-regions-get-wetter and contracted, and dry-areas-get-drier and expanded.

Cellulose nanofibers from lignocellulosic biomass of lemongrass using enzymatic hydrolysis: characterization and cytotoxicity assessment. - Priyanka Kumari; Gauri Pathak; Ruby Gupta; Deepika Sharma; Abha Meena (DARU Journal of Pharmaceutical Sciences, 2019)

North American extreme precipitation events and related large-scale meteorological patterns: a review of statistical methods, dynamics, modeling, and trends - Mathew Barlow; William J. Gutowski; John R. Gyakum; Richard W. Katz; Young-Kwon Lim; Russ S. Schumacher; Michael F. Wehner; Laurie Agel; Michael Bosilovich; Allison Collow; Alexander Gershunov; Richard Grotjahn; et al. (Climate Dynamics, 2019)
This paper surveys the current state of knowledge regarding large-scale meteorological patterns (LSMPs) associated with short-duration (less than 1 week) extreme precipitation events over North America. In contrast to teleconnections, which are typically defined based on the characteristic spatial variations of a meteorological field or on the remote circulation response to a known forcing, LSMPs are defined relative to the occurrence of a specific phenomenon—here, extreme precipitation—and with an emphasis on the synoptic scales that have a primary influence in individual events, have medium-range weather predictability, and are well-resolved in both weather and climate models. For the LSMP relationship with extreme precipitation, we consider the previous literature with respect to definitions and data, dynamical mechanisms, model representation, and climate change trends. There is considerable uncertainty in identifying extremes based on existing observational precipitation data and some limitations in analyzing the associated LSMPs in reanalysis data. Many different definitions of “extreme” are in use, making it difficult to directly compare different studies. Dynamically, several types of meteorological systems—extratropical cyclones, tropical cyclones, mesoscale convective systems, and mesohighs—and several mechanisms—fronts, atmospheric rivers, and orographic ascent—have been shown to be important aspects of extreme precipitation LSMPs. The extreme precipitation is often realized through mesoscale processes organized, enhanced, or triggered by the LSMP. Understanding of model representation, trends, and projections for LSMPs is at an early stage, although some promising analysis techniques have been identified and the LSMP perspective is useful for evaluating the model dynamics associated with extremes.

Correction to: Sub-cloud moist entropy curvature as a predictor for changes in the seasonal cycle of tropical precipitation - Bryce E. Harrop; Jian Lu; L. Ruby Leung (Climate Dynamics, 2019)

Sub-cloud moist entropy curvature as a predictor for changes in the seasonal cycle of tropical precipitation - Bryce E. Harrop; Jian Lu; L. Ruby Leung (Climate Dynamics, 2019)

An integrated genetic linkage map of Bixa orellana L. - Nayeli Romero-López; Francisco Luna-Martínez; Claudine Gallegos-Brito; Pedro Escobar-Turriza; Margarita Aguilar-Espinosa; Ruby Valdez-Ojeda; June Simpson; Renata Rivera-Madrid (Tree Genetics & Genomes, 2019)

Progress on the phylogeny of the Omphalotaceae: Gymnopus s. str., Marasmiellus s. str., Paragymnopus gen. nov. and Pusillomyces gen. nov. - Jadson J. S. Oliveira; Ruby Vargas-Isla; Tiara S. Cabral; Doriane P. Rodrigues; Noemia K. Ishikawa (Mycological Progress, 2019)

Simulation of climate characteristics and extremes of the Volta Basin using CCLM and RCA regional climate models - Deborah Darko; Kwaku A. Adjei; Emmanuel K. Appiah-Adjei; Samuel N. Odai; Emmanuel Obuobie; Ruby Asmah (Theoretical and Applied Climatology, 2019)

South Asian monsoon precipitation in CMIP5: a link between inter-model spread and the representations of tropical convection - Samson Hagos; L. Ruby Leung; Moetasim Ashfaq; Karthik Balaguru (Climate Dynamics, 2019)

Effects of seasonal and environmental changes on aquaculture production in tropical Lake Volta, Ghana - Emmanuel T. D. Mensah; Hederick R. Dankwa; Lauridsen L. Torben; Ruby Asmah; Benjamin B. Campion; Regina Edziyie (Aquaculture International, 2018)

Hexadecylated linear PEI self-assembled nanostructures as efficient vectors for neuronal gene delivery - Ruby Bansal; Brashket Seth; Shashikant Tiwari; Sadaf Jahan; Manisha Kumari; Aditya Bhushan Pant; Rajnish Kumar Chaturvedi; Pradeep Kumar; Kailash Chand Gupta (Drug Delivery and Translational Research, 2018)

Angiotensin Receptor Blockade by Inhibiting Glial Activation Promotes Hippocampal Neurogenesis Via Activation of Wnt/β-Catenin Signaling in Hypertension - Shahnawaz Ali Bhat; Ruby Goel; Shubha Shukla; Rakesh Shukla; Kashif Hanif (Molecular Neurobiology, 2018)

Angiotensin II Receptor Blockers Attenuate Lipopolysaccharide-Induced Memory Impairment by Modulation of NF-κB-Mediated BDNF/CREB Expression and Apoptosis in Spontaneously Hypertensive Rats - Ruby Goel; Shahnawaz Ali Bhat; Kashif Hanif; Chandishwar Nath; Rakesh Shukla (Molecular Neurobiology, 2018)

Copy number variation arising from gene conversion on the human Y chromosome - Wentao Shi; Andrea Massaia; Sandra Louzada; Ruby Banerjee; Pille Hallast; Yuan Chen; Anders Bergström; Yong Gu; Steven Leonard; Michael A. Quail; Qasim Ayub; Fengtang Yang; et al. (Human Genetics, 2018)

Genome editing in livestock: Are we ready for a revolution in animal breeding industry? - Jinxue Ruan; Jie Xu; Ruby Yanru Chen-Tsai; Kui Li (Transgenic Research, 2017)

Sustainability assessment of mine-affected communities in Ghana: towards ecosystems and livelihood restoration - Effah Kwabena Antwi; Wiafe Owusu-Banahene; John Boakye-Danquah; Ruby Mensah; Jacob Doku Tetteh; Masafumi Nagao; Kazuhiko Takeuchi (Sustainability Science, 2017)

Sources of errors in the simulation of south Asian summer monsoon in the CMIP5 GCMs - Moetasim Ashfaq; Deeksha Rastogi; Rui Mei; Danielle Touma; L. Ruby Leung (Climate Dynamics, 2017)

Heavy metal concentrations in soils and vegetation in urban areas of Quezon City, Philippines - Ian A. Navarrete; Christella C. Gabiana; Joan Ruby E. Dumo; Severino G. Salmo; Maria Aileen Leah G. Guzman; Nestor S. Valera; Emilyn Q. Espiritu (Environmental Monitoring and Assessment, 2017)

Pharmacokinetics and Biodistribution of GDC-0449 Loaded Micelles in Normal and Liver Fibrotic Mice - Rinku Dutta; Virender Kumar; Yang Peng; Ruby E. Evande; Jean L. Grem; Ram I. Mahato (Pharmaceutical Research, 2017)

Screening of Potato Cultivars to Potato Mop-Top Virus in Northwestern Pakistan - Muhammad Arif; Ghazala Ruby; Anayatur Rehman; Murad Ali; Shamsur Rehman (Potato Research, 2016)

Angiotensin Receptor Blockade Modulates NFκB and STAT3 Signaling and Inhibits Glial Activation and Neuroinflammation Better than Angiotensin-Converting Enzyme Inhibition - Shahnawaz Ali Bhat; Ruby Goel; Rakesh Shukla; Kashif Hanif (Molecular Neurobiology, 2016)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Uncertainty and feasibility of dynamical downscaling for modeling tropical cyclones for storm surge simulation - Zhaoqing Yang; Sourav Taraphdar; Taiping Wang; L. Ruby Leung; Molly Grear (Natural Hazards, 2016)

Mini-review: toxicity of mercury as a consequence of enzyme alteration - Ruby Ynalvez; Jose Gutierrez; Hector Gonzalez-Cantu (BioMetals, 2016)

Future hurricane storm surge risk for the U.S. gulf and Florida coasts based on projections of thermodynamic potential intensity - Karthik Balaguru; David R. Judi; L. Ruby Leung (Climatic Change, 2016)

Advances in Boerhaavia diffusa hairy root technology: a valuable pursuit for identifying strain sensitivity and up-scaling factors to refine metabolite yield and bioactivity potentials - Ruby Gupta; Pallavi Pandey; Sailendra Singh; Dhananjay Kumar Singh; Archana Saxena; Suaib Luqman; Dnyaneshwar U. Bawankule; Suchitra Banerjee (Protoplasma, 2016)

Circulating microRNA Signatures in Rodent Models of Pain - Rehman A. Qureshi; Yuzhen Tian; Marguerite K. McDonald; Kathryn E. Capasso; Sabrina R. Douglas; Ruby Gao; Irina A. Orlova; James E. Barrett; Seena K. Ajit; Ahmet Sacan (Molecular Neurobiology, 2016)

Polycystic ovarian syndrome (PCOS), related symptoms/sequelae, and breast cancer risk in a population-based case–control study - Jayeon Kim; Jennifer E. Mersereau; Nikhil Khankari; Patrick T. Bradshaw; Lauren E. McCullough; Rebecca Cleveland; Sumitra Shantakumar; Susan L. Teitelbuam; Alfred I. Neugut; Ruby T. Senie; Marilie D. Gammon (Cancer Causes & Control, 2016)

North American extreme temperature events and related large scale meteorological patterns: a review of statistical methods, dynamics, modeling, and trends - Richard Grotjahn; Robert Black; Ruby Leung; Michael F. Wehner; Mathew Barlow; Mike Bosilovich; Alexander Gershunov; William J. Gutowski; John R. Gyakum; Richard W. Katz; Yun-Young Lee; Young-Kwon Lim; et al. (Climate Dynamics, 2016)

Attributing runoff changes to climate variability and human activities: uncertainty analysis using four monthly water balance models - Shuai Li; Lihua Xiong; Hong-Yi Li; L. Ruby Leung; Yonas Demissie (Stochastic Environmental Research and Risk Assessment, 2016)

Parapheromones for Thynnine Wasps - Björn Bohman; Amir Karton; Ruby C. M. Dixon; Russell A. Barrow; Rod Peakall (Journal of Chemical Ecology, 2016)

Squalene Synthase Gene from Medicinal Herb Bacopa monniera: Molecular Characterization, Differential Expression, Comparative Modeling, and Docking Studies - Rishi K. Vishwakarma; Krunal Patel; Prashant Sonawane; Uma Kumari; Somesh Singh; Ruby; Shakeel Abbassi; Dinesh C. Agrawal; Hsin-Sheng Tsay; Bashir M. Khan (Plant Molecular Biology Reporter, 2015)

The de-correlation of westerly winds and westerly-wind stress over the Southern Ocean during the Last Glacial Maximum - Wei Liu; Jian Lu; L. Ruby Leung; Shang-Ping Xie; Zhengyu Liu; Jiang Zhu (Climate Dynamics, 2015)

The subchronic phencyclidine rat model: relevance for the assessment of novel therapeutics for cognitive impairment associated with schizophrenia - Sanna K. Janhunen; Heta Svärd; John Talpos; Gaurav Kumar; Thomas Steckler; Niels Plath; Linda Lerdrup; Trine Ruby; Marie Haman; Roger Wyler; Theresa M. Ballard (Psychopharmacology, 2015)

Three-dimensional printing of antibiotics-loaded poly-ε-caprolactone/poly(lactic-co-glycolic acid) scaffolds for treatment of chronic osteomyelitis - Jin-Hyung Shim; Min-Joo Kim; Ju Young Park; Ruby Gupta Pati; Young-Pil Yun; Sung Eun Kim; Hae-Ryong Song; Dong-Woo Cho (Tissue Engineering and Regenerative Medicine, 2015)

Mycological Profile and Antifungal Susceptibility of Fungal Isolates from Clinically Suspected Cases of Fungal Rhinosinusitis in a Tertiary Care Hospital in North India - Ruby Jain; Surinder K. Singhal; Nidhi Singla; Rajpal S. Punia; Jagdish Chander (Mycopathologia, 2015)

Projected changes in mean and interannual variability of surface water over continental China - GuoYong Leng; QiuHong Tang; MaoYi Huang; Yang Hong; Leung L. Ruby (Science China Earth Sciences, 2015)

Efficient shoots regeneration and genetic transformation of Bacopa monniera - Uma Kumari; Rishi K. Vishwakarma; Neha Gupta; Ruby; M. V. Shirgurkar; Bashir M. Khan (Physiology and Molecular Biology of Plants, 2015)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Investigating the nexus of climate, energy, water, and land at decision-relevant scales: the Platform for Regional Integrated Modeling and Analysis (PRIMA) - Ian Kraucunas; Leon Clarke; James Dirks; John Hathaway; Mohamad Hejazi; Kathy Hibbard; Maoyi Huang; Chunlian Jin; Michael Kintner-Meyer; Kerstin Kleese van Dam; Ruby Leung; Hong-Yi Li; et al. (Climatic Change, 2015)

Modeling high-impact weather and climate: lessons from a tropical cyclone perspective - James M. Done; Greg J. Holland; Cindy L. Bruyère; L. Ruby Leung; Asuka Suzuki-Parker (Climatic Change, 2015)

FLIPPER, a combinatorial probe for correlated live imaging and electron microscopy, allows identification and quantitative analysis of various cells and organelles - Jeroen Kuipers; Tjakko J. van Ham; Ruby D. Kalicharan; Anneke Veenstra-Algra; Klaas A. Sjollema; Freark Dijk; Ulrike Schnell; Ben N. G. Giepmans (Cell and Tissue Research, 2015)

Production of anti-cancer triterpene (betulinic acid) from callus cultures of different Ocimum species and its elicitation - Harshita Pandey; Pallavi Pandey; Sailendra Singh; Ruby Gupta; Suchitra Banerjee (Protoplasma, 2015)

Effect of Histone Deacetylase Inhibitor JNJ-26481585 in Pain - Kathryn E. Capasso; Melissa T. Manners; Rehman A. Quershi; Yuzhen Tian; Ruby Gao; Huijuan Hu; James E. Barrett; Ahmet Sacan; Seena K. Ajit (Journal of Molecular Neuroscience, 2015)

A comparative analysis of the impacts of climate change and irrigation on land surface and subsurface hydrology in the North China Plain - Guoyong Leng; Qiuhong Tang; Maoyi Huang; Lai-yung Ruby Leung (Regional Environmental Change, 2015)

Nitrogen stress-induced alterations in the leaf proteome of two wheat varieties grown at different nitrogen levels - Ruby Chandna; Altaf Ahmad (Physiology and Molecular Biology of Plants, 2015)

Assessment of uncertainties in the response of the African monsoon precipitation to land use change simulated by a regional model - Samson Hagos; L. Ruby Leung; Yongkang Xue; Aaron Boone; Fernando de Sales; Naresh Neupane; Maoyi Huang; Jin-Ho Yoon (Climate Dynamics, 2014)

Molecular cloning and characterization of genistein 4′-O-glucoside specific glycosyltransferase from Bacopa monniera - Ruby; R. J. Santosh Kumar; Rishi K. Vishwakarma; Somesh Singh; Bashir M. Khan (Molecular Biology Reports, 2014)

Genetic relationships among a collection of Musa germplasm by fluorescent-labeled SRAP - Ruby Valdez-Ojeda; Andrew James-Kay; José Roberto Ku-Cauich; Rosa María Escobedo-GraciaMedrano (Tree Genetics & Genomes, 2014)

A modeling study of coastal inundation induced by storm surge, sea-level rise, and subsidence in the Gulf of Mexico - Zhaoqing Yang; Taiping Wang; Ruby Leung; Kathy Hibbard; Tony Janetos; Ian Kraucunas; Jennie Rice; Benjamin Preston; Tom Wilbanks (Natural Hazards, 2014)

Exercise-induced oxidative stress and hypoxic exercise recovery - Christopher Ballmann; Graham McGinnis; Bridget Peters; Dustin Slivka; John Cuddy; Walter Hailes; Charles Dumke; Brent Ruby; John Quindry (European Journal of Applied Physiology, 2014)

Biopharmaceutical considerations and characterizations in development of colon targeted dosage forms for inflammatory bowel disease - Rajkumar Malayandi; Phani Krishna Kondamudi; P. K. Ruby; Deepika Aggarwal (Drug Delivery and Translational Research, 2014)

Eddy fluxes and sensitivity of the water cycle to spatial resolution in idealized regional aquaplanet model simulations - Samson Hagos; L. Ruby Leung; William I. Gustafson; Balwinder Singh (Climate Dynamics, 2014)

Functional Characterization of a Glucosyltransferase Specific to Flavonoid 7-O-Glucosides from Withania somnifera - R. J. Santosh Kumar; Ruby; Somesh Singh; Prashant D. Sonawane; R. K. Vishwakarma; B. M. Khan (Plant Molecular Biology Reporter, 2013)

Molecular characterization and differential expression studies of an oxidosqualene cyclase (OSC) gene of Brahmi (Bacopa monniera) - Rishi K. Vishwakarma; Prashant Sonawane; Somesh Singh; Uma Kumari; Ruby; Bashir M. Khan (Physiology and Molecular Biology of Plants, 2013)

Synthesis of piperazinyl benzothiazole/benzoxazole derivatives coupled with 1,3,4-oxadiazole-2-thiol: novel hybrid heterocycles as anticancer agents - M. S. R. Murty; B. Ramalingeswara Rao; Mohana Rao Katiki; Lekshmi R. Nath; Ruby John Anto (Medicinal Chemistry Research, 2013)

Erratum to: Floral diversity during Plio-Pleistocene Siwalik sedimentation (Kimin Formation) in Arunachal Pradesh, India, and its palaeoclimatic significance - Mahasin Ali Khan; Ruby Ghosh; Subir Bera; Robert A. Spicer; T. E. V. Spicer (Palaeobiodiversity and Palaeoenvironments, 2013)

Rationale for treating primary Sjögren’s syndrome patients with an anti-CD6 monoclonal antibody (Itolizumab) - Christelle Le Dantec; Ruby Alonso; Tinhinane Fali; Enrique Montero; Valérie Devauchelle; Alain Saraux; Jacques-Olivier Pers; Yves Renaudineau (Immunologic Research, 2013)

Impacts of enhanced CCN on the organization of convection and recent reduced counts of monsoon depressions - T. N. Krishnamurti; Andrew Martin; Ruby Krishnamurti; Anu Simon; Aype Thomas; Vinay Kumar (Climate Dynamics, 2013)

Molecular Cloning, Biochemical Characterization, and Differential Expression of an Acetyl-CoA C-Acetyltransferase Gene (AACT) of Brahmi (Bacopa monniera) - Rishi K. Vishwakarma; Ruby; Somesh Singh; Prashant D. Sonawane; Sameer Srivastava; Uma Kumari; R. J. Santosh Kumar; Bashir M. Khan (Plant Molecular Biology Reporter, 2013)

Genetic variants associated with breast cancer risk for Ashkenazi Jewish women with strong family histories but no identifiable BRCA1/2 mutation - Erica S. Rinella; Yongzhao Shao; Lauren Yackowski; Sreemanta Pramanik; Ruth Oratz; Freya Schnabel; Saurav Guha; Charles LeDuc; Christopher L. Campbell; Susan D. Klugman; Mary Beth Terry; Ruby T. Senie; et al. (Human Genetics, 2013)

Effect of angiotensin II on spatial memory, cerebral blood flow, cholinergic neurotransmission, and brain derived neurotrophic factor in rats - Santoshkumar Tota; Ruby Goel; Shakti Deep Pachauri; Rajasekar N.; Abul Kalam Najmi; Kashif Hanif; Chandishwar Nath (Psychopharmacology, 2013)

Interaction of marine Streptomyces compounds with selected cancer drug target proteins by in silico molecular docking studies - Amulya Ruby Lankapalli; K. Kannabiran (Interdisciplinary Sciences: Computational Life Sciences, 2013)

Effects of agricultural pesticides on the health of Rana pipiens frogs sampled from the field - M. S. Christin; L. Ménard; I. Giroux; D. J. Marcogliese; S. Ruby; D. Cyr; M. Fournier; P. Brousseau (Environmental Science and Pollution Research, 2013)

Treatment of hydrocarbon contamination under flow through conditions by using magnetite catalyzed chemical oxidation - M. Usman; P. Faure; C. Lorgeoux; C. Ruby; K. Hanna (Environmental Science and Pollution Research, 2013)

Synthesis and preliminary evaluation activity studies of novel 4-(aryl/heteroaryl-2-ylmethyl)-6-phenyl-2-[3-(4-substituted-piperazine-1-yl)propyl]pyridazin-3(2H)-one derivatives as anticancer agents - M. S. R. Murty; B. Ramalingeswara Rao; Kesur R. Ram; J. S. Yadav; Jayesh Antony; Ruby John Anto (Medicinal Chemistry Research, 2012)

Substrate use and biochemical response to a 3,211-km bicycle tour in trained cyclists - Dustin R. Slivka; Charles L. Dumke; Walter S. Hailes; John S. Cuddy; Brent C. Ruby (European Journal of Applied Physiology, 2012)

Complete genome sequence of a potyvirus infecting yam beans (Pachyrhizus spp.) in Peru - Segundo Fuentes; Bettina Heider; Ruby Carolina Tasso; Elisa Romero; Thomas zum Felde; Jan Frederik Kreuze (Archives of Virology, 2012)

ENSO anomalies over the Western United States: present and future patterns in regional climate simulations - Yongxin Zhang; Yun Qian; Valérie Dulière; Eric P. Salathé; L. Ruby Leung (Climatic Change, 2012)

Floral diversity during Plio-Pleistocene Siwalik sedimentation (Kimin Formation) in Arunachal Pradesh, India, and its palaeoclimatic significance - Mahasin Ali Khan; Ruby Ghosh; Subir Bera; Robert A. Spicer; T. E. V. Spicer (Palaeobiodiversity and Palaeoenvironments, 2011)

Synthesis and preliminary evaluation of 2-substituted-1,3-benzoxazole and 3-[(3-substituted)propyl]-1,3-benzoxazol-2(3H)-one derivatives as potent anticancer agents - M. S. R. Murty; Kesur R. Ram; Rayudu Venkateswara Rao; J. S. Yadav; Janapala Venkateswara Rao; Vino T. Cheriyan; Ruby John Anto (Medicinal Chemistry Research, 2011)

Simulations of precipitation using NRCM and comparisons with satellite observations and CAM: annual cycle - Aditya Murthi; Kenneth P. Bowman; L. Ruby Leung (Climate Dynamics, 2011)

Sulfur starvation and restoration affect nitrate uptake and assimilation in rapeseed - Gurjeet Kaur; Ruby Chandna; Renu Pandey; Yash Pal Abrol; Muhammad Iqbal; Altaf Ahmad (Protoplasma, 2011)

Does Prescribed Fire Benefit Wetland Vegetation? - Conception Flores; Dixie L. Bounds; Douglas E. Ruby (Wetlands, 2011)

Role of the atmospheric mean state on the initiation of the Madden-Julian oscillation in a tropical channel model - Pallav Ray; Chidong Zhang; Mitchell W. Moncrieff; Jim Dudhia; Julie M. Caron; L. Ruby Leung; Cindy Bruyere (Climate Dynamics, 2011)

Climate–soil–vegetation control on groundwater table dynamics and its feedbacks in a climate model - L. Ruby Leung; Maoyi Huang; Yun Qian; Xu Liang (Climate Dynamics, 2011)

Mitochondrial genomic divergence in coelacanths (Latimeria): slow rate of evolution or recent speciation? - Sudarto; Xandramaya C. Lalu; Janny D. Kosen; Agus H. Tjakrawidjaja; Ruby Vidia Kusumah; Bambang Sadhotomo; Kadarusman; Laurent Pouyaud; Jacques Slembrouck; Emmanuel Paradis (Marine Biology, 2010)

Regional climate model projections for the State of Washington - Eric P. Salathé; L. Ruby Leung; Yun Qian; Yongxin Zhang (Climatic Change, 2010)

The between and within day variation in gross efficiency - Dionne A. Noordhof; Jos J. de Koning; Teun van Erp; Bart van Keimpema; Daan de Ridder; Ruby Otter; Carl Foster (European Journal of Applied Physiology, 2010)

Genetic connectivity and historical demography of the blue barred parrotfish (Scarus ghobban) in the western Indian Ocean - Shakil Visram; Ming-Che Yang; Ruby Moothien Pillay; Sadri Said; Oskar Henriksson; Mats Grahn; Chaolun Allen Chen (Marine Biology, 2010)

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

Variability in Indian bread wheat (Triticum aestivum L.) varieties differing in nitrogen efficiency as assessed by microsatellite markers - Ruby Chandna; Sarika Gupta; Altaf Ahmad; Muhammad Iqbal; Manoj Prasad (Protoplasma, 2010)

Phylogeny of Rhododendron subgenus Hymenanthes based on chloroplast DNA markers: between-lineage hybridisation during adaptive radiation? - Richard I. Milne; Chantel Davies; Ruby Prickett; Lucy H. Inns; David F. Chamberlain (Plant Systematics and Evolution, 2010)

Fenton-like oxidation and mineralization of phenol using synthetic Fe(II)–Fe(III) green rusts - Khalil Hanna; Tiangoua Kone; Christian Ruby (Environmental Science and Pollution Research, 2010)

Space-time structures of earthquakes - T. N. Krishnamurti; Ruby Krishnamurti; Anitha D. Sagadevan; Arindam Chakraborty; William K. Dewar; Carol Anne Clayson; James F. Tull (Meteorology and Atmospheric Physics, 2009)

Predicting future threats to the long-term survival of Gila trout using a high-resolution simulation of climate change - Thomas L. Kennedy; David S. Gutzler; Ruby L. Leung (Climatic Change, 2009)

Non-coding RNAs revealed during identification of genes involved in chicken immune responses - Marie-Laure Endale Ahanda; Thomas Ruby; Håkan Wittzell; Bertrand Bed’Hom; Anne-Marie Chaussé; Veronique Morin; Anne Oudin; Catherine Chevalier; John R. Young; Rima Zoorob (Immunogenetics, 2009)

Separation of rifting and lithospheric folding signatures in the NW-Alpine foreland - O. Bourgeois; M. Ford; M. Diraison; C. Le Carlier de Veslud; M. Gerbault; R. Pik; N. Ruby; S. Bonnet (International Journal of Earth Sciences, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Solitary Foraging in the Ancestral South American Ant, Pogonomyrmex vermiculatus. Is it Due to Constraints in the Production or Perception of Trail Pheromones? - Hugo Torres-Contreras; Ruby Olivares-Donoso; Hermann M. Niemeyer (Journal of Chemical Ecology, 2007)

The effect of highly active antiretroviral therapy on outcome of central nervous system herpesviruses infection in Cuban human immunodeficiency virus-infected individuals - Pedro Ariel Martínez; René Díaz; Daniel González; Lisset Oropesa; Ruby González; Lissette Pérez; Jenniffer Viera; Vivian Kourí (Journal of NeuroVirology, 2007)

Characterisation of a cluster of TRIM-B30.2 genes in the chicken MHC B locus - Thomas Ruby; Bertrand Bed’Hom; Hakan Wittzell; Véronique Morin; Anne Oudin; Rima Zoorob (Immunogenetics, 2005)

A diagnostic model for green productivity assessment of manufacturing processes - Ruby Pineda-Henson; Alvin B. Culaba (The International Journal of Life Cycle Assessment, 2004)

Discrepancies in Bacterial Recovery from Dental Unit Water Samples on R2A Medium and a Commercial Sampling Device - Richard S. Smith; Silvia A. Pineiro; Ruby Singh; Elaine Romberg; Mohamed E. Labib; Henry N. Williams (Current Microbiology, 2004)

Mid-Century Ensemble Regional Climate Change Scenarios for the Western United States - L. Ruby Leung; Yun Qian; Xindi Bian; Warren M. Washington; Jongil Han; John O. Roads (Climatic Change, 2004)

Exposure of leopard frogs to a pesticide mixture affects life history characteristics of the lungworm Rhabdias ranae - A. D. Gendron; D. J. Marcogliese; S. Barbeau; M.-S. Christin; P. Brousseau; S. Ruby; D. Cyr; M. Fournier (Oecologia, 2003)

Characterization of Microbial Communities from Coastal Waters using Microarrays - O. Colin Stine; Amy Carnahan; Ruby Singh; Jan Powell; Jon P. Furuno; Alicia Dorsey; Ellen Silbergeld; Henry N. Williams; J. Glenn Morris (Environmental Monitoring and Assessment, 2003)

Elevation Dependence of Winter Wheat Production in Eastern Washington State with Climate Change: A Methodological Study - Allison M. Thomson; Robert A. Brown; Steven J. Ghan; R. Cesar Izaurralde; Norman J. Rosenberg; L. Ruby Leung (Climatic Change, 2002)

Evaluating Environmental Performance of Pulp and Paper Manufacturing Using the Analytic Hierarchy Process and Life‐Cycle Assessment - Ruby Pineda‐Henson; Alvin B. Culaba; Guillermo A. Mendoza (Journal of Industrial Ecology, 2002)
Summary This article addresses the need for a structured and compre‐hensive methodology for assessing the environmental perfor‐mance of manufacturing processes. The analytic hierarchy pro‐cess (AHP) is used as the basic framework for analyzing environmental impacts and improvement options following a streamlined life‐cycle assessment (LCA) approach that is fo‐cused on the manufacturing operation. The multicriteria de‐cision analysis approach of the AHP is consistent with the LCA concept because the environmental factors can be hierarchi‐cally structured into impacts and improvement options. Its po‐tential as a valuation tool for impact and improvement assess‐ment addresses both qualitative and quantitative issues in environmental decision making. Through application to a pulp and paper manufacturing case study, the viability of the AHP for evaluating environmen‐tal impacts and prioritizing process improvement options rela‐tive to these impacts is demonstrated. AHP was used to pro‐vide a quantitative tool for the design of a set of weighting factors for impact and improvement analyses.

TheVibrio fischeri sapABCDF locus is required for normal growth, both in culture and in symbiosis - Claudia Lupp; Robert E. W. Hancock; Edward G. Ruby (Archives of Microbiology, 2002)

Chemical Composition of Fruits and Leaves Eaten by Short-Nosed Fruit Bat, Cynopterus sphinx - J. Ruby; P. T. Nathan; J. Balasingh; T. H. Kunz (Journal of Chemical Ecology, 2000)

Chromosomal localization of CCS, the copper chaperone for Cu/Zn superoxide dismutase - Thomas B. Bartnikas; Darrel J. Waggoner; Ruby Leah B. Casareno; Roger Gaedigk; Robert A. White; Jonathan D. Gitlin (Mammalian Genome, 2000)

Manatee Mortality in Puerto Rico - Antonio A. Mignucci-Giannoni; Ruby A. Montoya-Ospina † , Nild (Environmental Management, 2000)

Sublethal Lead Affects Pituitary Function of Rainbow Trout During Exogenous Vitellogenesis - S. M. Ruby; R. Hull; P. Anderson (Archives of Environmental Contamination and Toxicology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Cryptic luminescence in the cold-water fish pathogen Vibrio salmonicida - P. M. Fidopiastis; Henning Sørum; E. G. Ruby (Archives of Microbiology, 1999)

The response of trout and zebrafish embryos to low and high boron concentrations is U-shaped - Ruby I. Rowe; Collen Bouzan; Sam Nabili; Curtis D. Eckhert (Biological Trace Element Research, 1998)

Growth and flagellation of Vibrio fischeri during initiation of the sepiolid squid light organ symbiosis - E. G. Ruby; L. M. Asato (Archives of Microbiology, 1993)

Tuber yield, soft rot resistance, bruising resistance and processing quality in a population of potato (cv. crystal) somaclones - R. J. Taylor; G. A. Secor; C. L. Ruby; P. H. Orr (American Journal of Potato Research, 1993)

Changes in brain dopamine levels, oocyte growth and spermatogenesis in rainbow trout,Oncorhynchus mykiss, following sublethal cyanide exposure - Attila Szabo; Sylvia M. Ruby; Frank Rogan; Zalman Amit (Archives of Environmental Contamination and Toxicology, 1991)

A study of suspended particulate matter in Lahore (Pakistan) - K. Hussain; Ruby Riffat; A. Shaukat; M. Ashraf Siddiqui (Advances in Atmospheric Sciences, 1990)

Plasma vitellogenin levels in pre-spawning rainbow trout,Oncorhynchus mykiss, during acid exposure - Robert L. Roy; Sylvia M. Ruby; David R. Idler; Ying So (Archives of Environmental Contamination and Toxicology, 1990)

Unbalanced growth as a normal feature of development of Bdellovibrio bacteriovorus - K. M. Gray; E. G. Ruby (Archives of Microbiology, 1989)

Changes in plasma, liver, and ovary vitellogenin in landlocked atlantic salmon following exposure to sublethal cyanide - Sylvia M. Ruby; David R. Idler; Ying Peng So (Archives of Environmental Contamination and Toxicology, 1987)

The effect of sublethal cyanide exposure on plasma viteliogenin levels in rainbow trout (Salmo gairdneri) during early vitellogenesis - Sylvia M. Ruby; David R. Idler; Ying Peng So (Archives of Environmental Contamination and Toxicology, 1986)

Effect of sublethal pentachlorophenol on early oogenesis in maturing female rainbow trout (Salmo gairdneri) - James J. Nagler; Prasad Aysola; Sylvia M. Ruby (Archives of Environmental Contamination and Toxicology, 1986)

The effect of sublethal cyanide on vitellogenic parameters in rainbow troutSalmo gairdneri - Helena Da Costa; Sylvia M. Ruby (Archives of Environmental Contamination and Toxicology, 1984)

Histological and quantitative effects of sublethal cyanide exposure on oocyte development in rainbow trout - Judith A. Lesniak; Sylvia M. Ruby (Archives of Environmental Contamination and Toxicology, 1982)

Effects of pulse exposure to sublethal levels of hydrogen cyanide on reproduction of American flagfish - S. K. Cheng; S. M. Ruby (Archives of Environmental Contamination and Toxicology, 1981)

Inhibition of spermatogenesis in rainbow trout during chronic cyanide poisoning - Sylvia M. Ruby; D. George Dixon; Grard Leduc (Archives of Environmental Contamination and Toxicology, 1979)

Hb Mobile [?2?2 73(E17)Asp ? Val]: A new variant - Rose G. Schneider; Thomas S. Hosty; Gary Tomlin; Ruby Atkins; Bernadine Brimhall; Richard T. Jones (Biochemical Genetics, 1975)